Incorporating CT-Derived Body Composition Analysis Into the Global Leadership Initiative on Malnutrition Criteria Is Associated With Overall Survival: Findings From an International Cancer Cohort - Clodagh Scannell; Erin Stella Sullivan; Ross D. Dolan; Josh McGovern; Marie Fallon; Barry J. Laird; Derek G. Power; Aoife M. Ryan (Journal of the Academy of Nutrition and Dietetics, 2026)

Freshwater biodiversity in a rapidly changing Arctic: An expert horizon scan of key research questions - Joseph M. Culp; Michael Power; Kirsten S. Christoffersen; Willem Goedkoop; Kimmo K. Kahilainen; Milla Rautio; Fernando Chaguaceda; Marie-Pier Hébert; Sanne M. Moedt; Dermot Antoniades; Simon Belle; Daniel Bolnick; et al. (Ambio, 2026)
Arctic freshwater biodiversity is rapidly changing due to climate warming, resource extraction, infrastructure development, and landscape transformation. To improve understanding, predict future responses, and inform policy formulation, research needs must be clearly identified. Using a horizon scan survey, Arctic freshwater experts from government, international agencies, and Indigenous Peoples identified 77 biodiversity research questions with 17 highlighted as most important for near term assessment. These questions span nine thematic categories: biodiversity and taxonomic challenges, hydrological change, productivity and food webs, ecosystem connectivity, methods, monitoring and assessment, permafrost change, winter ecology, anthropogenic development, and Indigenous Knowledge. Climate change emerged as the major driver among all categories and research questions. A key priority identified was the urgent need for long-term, harmonized monitoring programs among Arctic countries. Multiple knowledge gaps detected suggest that circumpolar research collaborations are required to tackle these issues.

Nutrient Enrichment Increases Grassland Biomass Sensitivity to Interannual Precipitation Variation - Ingrid J. Slette; Eric W. Seabloom; Carlos Alberto Arnillas; Jonathan D. Bakker; Dana Blumenthal; Jane A. Catford; Scott L. Collins; Nico Eisenhauer; Philip A. Fay; Magda Garbowski; Sylvia Haider; W. Stanley Harpole; et al. (Global Change Biology, 2026)
Primary production underpins much of ecosystem functioning and is often limited by nutrient and water availability. Ongoing global increases in nutrient inputs and interannual precipitation variability are thus likely to impact primary production, with unclear consequences for interannual variability in plant biomass. We used data from 35 grasslands in the Nutrient Network coordinated fertilization experiment to test if nutrient addition alters the response of plant biomass to year‐to‐year variation in growing season precipitation, and whether the effects of nutrient addition vary with factors such as site aridity or plant community composition. Nutrient addition increased biomass (by an average of 46% across sites), rain‐use efficiency (by 48%), and the sensitivity of biomass to interannual variation in precipitation (i.e., larger increase in biomass in wet years; by 13%), but did not change the strength of the interannual precipitation‐biomass correlation. Both sensitivity and correlation strength were higher in more arid sites, regardless of nutrient addition. These results suggest that grassland ecosystem functioning may become more variable from year to year as nutrient enrichment increases biomass sensitivity to precipitation and precipitation becomes more variable.

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Understanding the impacts of hydropower development on people, fish and the environment on the Madeira River of Amazonia, Brazil - Shannon H. Clarke; Maria Clara B. T. Cavalcanti; Vivian M. Nguyen; Taylor D. Ward; Eduardo G. Martins; Michael Power; Gustavo Hallwass; Priscila F. M. Lopes; Steven J. Cooke (Environmental Management, 2026)

Millennial-scale fire and climate dynamics in the world's largest tropical wetland show emerging fire threat to flooded ecosystems - Bronwen S. Whitney; Danilo M. Neves; Nicholas J.D. Loughlin; Carlos D'Apolito; Carla Coblinski Tavares; Emma P. Hocking; Francis E. Mayle; Mitchell J. Power; Aguinaldo Silva; Mario L. Assine (Global and Planetary Change, 2026)

Multi-millennial reconstruction of fire return intervals from a fynbos – Afrotemperate forest ecotone in the Cape Floristic Region, South Africa: Paleoecological implications for present-day management - Stella G. Mosher; Mitchell J. Power; Lynne J. Quick; Brian M. Chase; Torsten Haberzettl; Thomas Kasper; Simon C. Brewer; David R. Braun; J. Tyler Faith (Global and Planetary Change, 2026)

Nutrient Transfer Dynamics of Anadromous Alewives (Alosa pseudoharengus) in Freshwater Spawning and Nursery Habitats - Robert E. Vincent; John M. Logan; John J. Sheppard; Michael Power; Stephen T. Hurley; Kevin Bennett (Estuaries and Coasts, 2026)
River herring (alewife, Alosa pseudoharengus and blueback herring, A . aestivalis ) can act as vectors of nutrient transfer between marine and freshwater environments. Adult river herring can transfer marine-derived nutrients to freshwater ecosystems during spawning migrations through excretions and direct consumption of adults, eggs, and early phase juveniles by freshwater scavengers and predators. Adults and juveniles can transfer nutrients derived during freshwater residency back to the marine environment following emigration and the same excretion and consumption mechanisms. Potential nutrient transfers were assessed by applying carbon, nitrogen, and sulfur stable isotope analyses to a collection of juvenile and adult alewives, baseline food web components, and freshwater fish predators in three ponds in southeastern Massachusetts USA. Out-migrating adult alewife tissue stable isotope values were lower for both carbon and sulfur but higher for nitrogen than in-migrating conspecifics reflecting incorporation of freshwater-derived nutrients. Most juvenile alewife stable isotope values were at steady state with freshwater food webs at the time of sampling reflecting additional export of freshwater-derived nutrients with their eventual emigration to the marine environment. Stable isotope-based detection of marine-derived nutrients in freshwater predators was limited to catadromous elvers ( Anguilla rostrata ), anadromous white perch ( Morone americana ), and semi-anadromous yellow perch ( Perca flavescens ) with no marine-derived nutrients detected in resident freshwater fish predators. However, juvenile alewives were observed in stomachs of smallmouth ( Micropterus dolomieu ) and largemouth bass ( M . nigricans ). Results further inform current alewife ecosystem-level interactions with the marine and freshwater environments that they occupy during different life history phases for the many coastal watersheds in New England.

Evaluating climatic and anthropogenic drivers of fire activity over four millennia at Eilandvlei, southern Cape coast, South Africa - Stella G. Mosher; Mitchell J. Power; Brian M. Chase; Lynne J. Quick; Torsten Haberzettl; Thomas Kasper; David R. Braun; J. Tyler Faith (Quaternary Science Reviews, 2025)

A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

Quantifying the contribution of biogenic iron sulfides to magnesite formation in the Basque Lakes, British Columbia, Canada - Colton J. Vessey; Maija J. Raudsepp; Maria L. Arizaleta; Sasha Wilson; Anna L. Harrison; Kelly J. Rozanitis; Helen E.A. Brand; Kurt O. Konhauser; Kwon Rausis; Ian M. Power (Chemical Geology, 2025)

Multiple global change factors and the long‐term dynamics of harmful algal blooms in the North Sea - Karen M. Brandenburg; Julian Merder; Andrea Budiša; Anne Marie Power; Catharina J. M. Philippart; Anna M. Michalak; Tim J. van den Broek; Dedmer B. Van de Waal (Limnology and Oceanography, 2025)
The North Sea has been identified as an area where the impacts of climate change and de‐eutrophication efforts are already apparent, specifically on phytoplankton communities, with shifts in biogeography, altered species composition, and increased biomass of harmful algal bloom (HAB) species. Here, we test whether environmental changes in the Dutch North Sea are associated with changes in the abundances of HAB species and if the probability of blooms has increased over the past two decades. We do so by using generalized additive and logistic regression models, respectively. Results show that Phaeocystis globosa and potential ASP (amnesic shellfish poisoning) and DSP (diarrhetic shellfish poisoning) toxin‐producing species have increased in abundance along the coast over the period 2000–2018, despite overall declines in total phytoplankton biomass over the same period. Conversely, the abundance of potential ASP producers and particularly P. globosa declined in the more central areas of the North Sea. The probability of blooms, which varied across months during the season, generally increased. Environmental factors associated with these increases in the probability of HABs included increasing sea surface temperatures (for potential ASP and DSP toxin producers), possibly related to summer stratification of the water column, and increasing total nitrogen (TN) : total phosphorus (TP) ratios (for potential ASP and DSP toxin producers and P. globosa ) due to de‐eutrophication efforts that more effectively reduced TP than TN. Our results demonstrate how long‐term changes in HAB species abundances in the North Sea are associated with shifts in multiple global change factors that together may lead to intensified HAB development.

TropiRoot 1.0: Database of tropical root characteristics across environments - Amanda L. Cordeiro; Daniela F. Cusack; Nathaly Guerrero‐Ramírez; Richard J. Norby; Laura Toro; Michelle Y. Wong; S. Joseph Wright; Kristine Grace M. Cabugao; Kelly M. Andersen; Lucia Fuchslueger; Colleen M. Iversen; Fiona Soper; et al. (Ecology, 2025)
Tropical ecosystems contain the world's largest biodiversity of vascular plants. Yet, our understanding of tropical functional diversity and its contribution to global diversity patterns is constrained by data availability. This discrepancy underscores an urgent need to bridge data gaps by incorporating comprehensive tropical root data into global datasets. Here, we provide a database of tropical root characteristics. This new database, TropiRoot 1.0, will be instrumental in evaluating an array of hypotheses pertaining to root functional ecology and plant biogeography, both within the tropics and relative to other global biomes. The data compilation was conducted by the TropiRoot Initiative, in partnership with the Fine‐Root Ecology Database (FRED) and the Global Root Trait (GRooT) database, Colorado State University (CSU) and the Smithsonian Tropical Research Institute (STRI). Literature search and data extraction were conducted between 2020 and 2024. Literature was identified using Web of Science, Scopus, and complemented using the expert knowledge of members of TropiRoot. To provide broad environmental and geographical distributions, literature searches included root characteristics (traits) across global change drivers, natural gradients, and from different continents. We adopted FRED standardized data columns and streamlined the format to enhance accessibility for data extraction across various user groups. This optimized framework resulted in a smaller, yet comprehensive datasheet. To make the database compatible with other global root trait initiatives, column identification was standardized following the codes provided by FRED. These efforts culminated in data extracted from 104 new sources, resulting in more than 8000 rows of data (either species or community data). Most of the data in TropiRoot 1.0 include root characteristics such as root biomass, morphology, root dynamics, mass fraction, architecture, anatomy, physiology, and root chemistry. This initiative represents a 30% increase in the currently available data for tropical roots in FRED. TropiRoot 1.0 contains root characteristics from 25 different countries, where seven are located in Asia, six in South America, five in Central America and the Caribbean, four in Africa, two in North America, and 1 in Oceania. Due to the volume of data, when ancillary data were available, including soil data, these data were either extracted and included in the database or its availability was recorded in an additional column. Multiple contributors checked the entries for outliers during the collation process to ensure data quality. For text‐based observations, we examined all cells to ensure that their content relates to their specific categories. For numerical observations, we ordered each numerical value from least to greatest and plotted the values, checking apparent outliers against the data in their respective sources and correcting or removing incorrect or impossible values. Some data (soil and aboveground) have different columns for the same variable presented in different units, including originally published units, but root characteristics data had units converted to match those reported in FRED. By filling a gap from global databases, TropiRoot 1.0 expands our knowledge of otherwise so far underrepresented regions and our ability to assess global trends. This advancement can be used to improve tropical forest representation in vegetation models. The data are freely available and should be cited when used.

The nature of microbial diversity and assembly in the Nebraska Sandhills depends on organismal identity and habitat type - Kaitlin Gattoni; Eli M. S. Gendron; J. Parr McQueen; Kirsten Powers; Thomas O. Powers; Mary J. Harner; Jessica R. Corman; Dorota L. Porazinska (Community Ecology, 2025)

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Effects of a Fruit and Vegetable Supplement on the Skin Carotenoid Scores in Healthy Adults: A Pilot Study - R. Brooks; C. Washburn; M. Powers; J. Mayo; A. Landry (Journal of the Academy of Nutrition and Dietetics, 2024)

Correction: Progress in the analysis of English Channel loliginid squid diets using DNA-metabarcoding techniques - A. Larivain; C. Zatylny-Gaudin; E. Gonzalez; G. J. Pierce; A. M. Power; J. P. Robin (Marine Biology, 2024)

From field station to forecast: managing data at the Alaska Volcano Observatory - Michelle L. Coombs; Cheryl E. Cameron; Hannah R. Dietterich; Eleanor S. Boyce; Aaron G. Wech; Ronni Grapenthin; Kristi L. Wallace; Tom Parker; Taryn Lopez; Scott Crass; David Fee; Matthew M. Haney; et al. (Bulletin of Volcanology, 2024)

TRPC Channels Activated by G Protein-Coupled Receptors Drive Ca2+ Dysregulation Leading to Secondary Brain Injury in the Mouse Model - Jasneet Parmar; Georg von Jonquieres; Nagarajesh Gorlamandala; Brandon Chung; Amanda J. Craig; Jeremy L. Pinyon; Lutz Birnbaumer; Matthias Klugmann; Andrew J. Moorhouse; John M. Power; Gary D. Housley (Translational Stroke Research, 2024)
Canonical transient receptor potential (TRPC) non-selective cation channels, particularly those assembled with TRPC3, TRPC6, and TRPC7 subunits, are coupled to G αq -type G protein-coupled receptors for the major classes of excitatory neurotransmitters. Sustained activation of this TRPC channel-based pathophysiological signaling hub in neurons and glia likely contributes to prodigious excitotoxicity-driven secondary brain injury expansion. This was investigated in mouse models with selective Trpc gene knockout (KO). In adult cerebellar brain slices, application of glutamate and the class I metabotropic glutamate receptor agonist (S)-3,5-dihydroxyphenylglycine to Purkinje neurons expressing the GCaMP5g Ca 2+ reporter demonstrated that the majority of the Ca 2+ loading in the molecular layer dendritic arbors was attributable to the TRPC3 effector channels ( Trpc3 KO compared with wildtype (WT)). This Ca 2+ dysregulation was associated with glutamate excitotoxicity causing progressive disruption of the Purkinje cell dendrites (significantly abated in a GAD67-GFP - Trpc3 KO reporter brain slice model). Contribution of the G αq -coupled TRPC channels to secondary brain injury was evaluated in a dual photothrombotic focal ischemic injury model targeting cerebellar and cerebral cortex regions, comparing day 4 post-injury in WT mice, Trpc3 KO , and Trpc1/3/6/7 quadruple knockout ( Trpc QKO ), with immediate 2-h (primary) brain injury. Neuroprotection to secondary brain injury was afforded in both brain regions by Trpc3 KO and Trpc QKO models, with the Trpc QKO showing greatest neuroprotection. These findings demonstrate the contribution of the G αq -coupled TRPC effector mechanism to excitotoxicity-based secondary brain injury expansion, which is a primary driver for mortality and morbidity in stroke, traumatic brain injury, and epilepsy.

Southern Flounder: Major Milestones and Remaining Knowledge Gaps in Their Biology, Ecology, and Fishery Management - Stephen R. Midway; Frederick S. Scharf; Michael A. Dance; Nancy J. Brown-Peterson; Joseph C. Ballenger; Nicolette S. Beeken; Russell J. Borski; Tanya L. Darden; Kenneth A. Erickson; Troy M. Farmer; Ashley Fincannon; John Godwin; et al. (Reviews in Fisheries Science & Aquaculture, 2024)

Progress in the analysis of English Channel loliginid squid diets using DNA-metabarcoding techniques - A. Larivain; C. Zatylny-Gaudin; E. Gonzalez; G. J. Pierce; A. M. Power; J. P. Robin (Marine Biology, 2024)

Tropical root responses to global changes: A synthesis - Daniela Yaffar; Laynara F. Lugli; Michelle Y. Wong; Richard J. Norby; Shalom D. Addo‐Danso; Marie Arnaud; Amanda L. Cordeiro; Lee H. Dietterich; Milton H. Diaz‐Toribio; Ming Y. Lee; Om Prakash Ghimire; Chris M. Smith‐Martin; et al. (Global Change Biology, 2024)
Tropical ecosystems face escalating global change. These shifts can disrupt tropical forests' carbon (C) balance and impact root dynamics. Since roots perform essential functions such as resource acquisition and tissue protection, root responses can inform about the strategies and vulnerabilities of ecosystems facing present and future global changes. However, root trait dynamics are poorly understood, especially in tropical ecosystems. We analyzed existing research on tropical root responses to key global change drivers: warming, drought, flooding, cyclones, nitrogen (N) deposition, elevated (e) CO 2 , and fires. Based on tree species‐ and community‐level literature, we obtained 266 root trait observations from 93 studies across 24 tropical countries. We found differences in the proportion of root responsiveness to global change among different global change drivers but not among root categories. In particular, we observed that tropical root systems responded to warming and eCO 2 by increasing root biomass in species‐scale studies. Drought increased the root: shoot ratio with no change in root biomass, indicating a decline in aboveground biomass. Despite N deposition being the most studied global change driver, it had some of the most variable effects on root characteristics, with few predictable responses. Episodic disturbances such as cyclones, fires, and flooding consistently resulted in a change in root trait expressions, with cyclones and fires increasing root production, potentially due to shifts in plant community and nutrient inputs, while flooding changed plant regulatory metabolisms due to low oxygen conditions. The data available to date clearly show that tropical forest root characteristics and dynamics are responding to global change, although in ways that are not always predictable. This synthesis indicates the need for replicated studies across root characteristics at species and community scales under different global change factors.

Climate‐related variation of metabolic rate across the distribution of a broadly tolerant invasive forest pest - Sean D. Powers; Lily M. Thompson; Dylan Parry; Kristine L. Grayson; Eloy Martinez; Salvatore J. Agosta (Journal of Biogeography, 2024)
Aim Metabolic rate is a widely studied physiological species trait related to energetics, climate, and geographical distributions. Hypotheses have been proposed to explain variation in metabolic rate, but evidence has been mixed due to the limited sampling scope of intraspecific studies. Successful biological invasions offer a unique opportunity to examine the development of intraspecific physiological variation and how it relates to climate, invasive spread and species range limits. The aim of this study was to determine if metabolic rate variation across the spongy moth invasive range was consistent with a pattern of adaptation to local climate. Location Northeastern United States of America. Taxon Lymantria dispar dispar L. (Lepidoptera: Erebidae). Methods Larvae were sourced from 14 populations across the invasion front and interior of the current L. d. dispar invasive range and were reared at a constant temperature. Routine metabolic rates (RMR) of larvae were assayed at three ecologically relevant temperatures. These data were analysed to determine if there were differences in RMR and temperature sensitivity of RMR among populations. Population‐level variation in RMR was then analysed as a function of local climate and geographical position to test for patterns consistent with local adaptation. Results Larval RMR showed significant variation among populations across all assay temperatures, but there was no difference in temperature sensitivity (i.e. slope). This variation followed a positive latitudinal cline with RMR increasing from the southern range to the north. This cline also showed a significant relationship with local climate variables. Main Conclusions Larval metabolic rate variation was consistent with a pattern of adaptation by L. d. dispar to divergent climates across its invasive range. These results indicated that thermal adaptation of whole‐organism physiology may play a key role in promoting species spread and expansion for biological invasions like L. d. dispar .

Habitat-dependent metabolic costs for a wild cold-water fish - Benjamin L. Hlina; Daniel M. Glassman; Elodie J. I. Lédée; Liane B. Nowell; Julie E. Claussen; David P. Philipp; J. Ellen Marsden; Michael Power; Steven J. Cooke (Aquatic Sciences, 2024)

Magnesite everywhere: Formation of carbonates in the alkaline lakes and playas of the Cariboo Plateau, British Columbia, Canada - Maija J. Raudsepp; Sasha Wilson; Nina Zeyen; Maria L. Arizaleta; Ian M. Power (Chemical Geology, 2024)

Dominance of net autotrophy in arid landscape low relief polar lakes, Nunavut, Canada - Paola Ayala‐Borda; Matthew J. Bogard; Guillaume Grosbois; Vilmantas Prėskienis; Joseph M. Culp; Michael Power; Milla Rautio (Global Change Biology, 2024)
The Arctic is the fastest warming biome on the planet, and environmental changes are having striking effects on freshwater ecosystems that may impact the regional carbon cycle. The metabolic state of Arctic lakes is often considered net heterotrophic, due to an assumed supply of allochthonous organic matter that supports ecosystem respiration and carbon mineralization in excess of rates of primary production. However, lake metabolic patterns vary according to regional climatic characteristics, hydrological connectivity, organic matter sources and intrinsic lake properties, and the metabolism of most Arctic lakes is unknown. We sampled 35 waterbodies along a connectivity gradient from headwater to downstream lakes, on southern Victoria Island, Nunavut, in an area characterized by low precipitation, organic‐poor soils, and high evaporation rates. We evaluated whether lakes were net autotrophic or heterotrophic during the open water period using an oxygen isotopic mass balance approach. Most of the waterbodies were autotrophic and sites of net organic matter production or close to metabolic equilibrium. Autotrophy was associated with higher benthic primary production, as compared to its pelagic counterpart, due to the high irradiance reaching the bottom and efficient internal carbon and nutrient cycling. Highly connected midstream and downstream lakes showed efficient organic matter cycling, as evidenced by the strong coupling between gross primary production (GPP) and ecosystem respiration, while decoupling was observed in some headwater lakes with significantly higher GPP. The shallow nature of lakes in the flat, arid region of southern Victoria Island supports net autotrophy in most lakes during the open water season. Ongoing climate changes that lengthen the ice‐free irradiance period and increase rates of nutrient evapoconcentration may further promote net autotrophy, with uncertain long‐term effects for lake functioning.

Tracking kelp-type seaweed fuel in the archaeological record through Raman spectroscopy of charred particles: examples from the Atacama Desert coast - Luca Sitzia; Ximena Power; Debora Zurro; Jean Paul Maalouf; José Cárcamo; Kristopher Chandía; J. M. Alonso Vega; César Borie; Constanza Roa; Claudia Silva; Diego Salazar; Sebastián Vivanco; et al. (Archaeological and Anthropological Sciences, 2023)

Novel estimation of gear selectivity using a concurrent mass mortality event: A case study using red drum (Sciaenops ocellatus) in the northern Gulf of Mexico - Sean P. Powers; Crystal L. Hightower; John M. Hoenig; Jeffrey D. Plumlee; T. Reid Nelson; J. Marcus Drymon (Fisheries Research, 2023)

The Western Lake Erie culture collection: A promising resource for evaluating the physiological and genetic diversity of Microcystis and its associated microbiome - Colleen E. Yancey; E. Anders Kiledal; Subba Rao Chaganti; Vincent J. Denef; Reagan M. Errera; Jacob T. Evans; Lauren N. Hart; Dragan Isailovic; William S. James; Jenan J. Kharbush; Jeffrey A. Kimbrel; Wei Li; et al. (Harmful Algae, 2023)

High-resolution entry and exit surface dosimetry in a 1.5 T MR-linac - E. Patterson; P. Stokes; D. Cutajar; A. Rosenfeld; J. Baines; P. Metcalfe; M. Powers (Physical and Engineering Sciences in Medicine, 2023)
The magnetic field of a transverse MR-linac alters electron trajectories as the photon beam transits through materials, causing lower doses at flat entry surfaces and increased doses at flat beam-exiting surfaces. This study investigated the response of a MOSFET detector, known as the MO Skin ™, for high-resolution surface and near-surface percentage depth dose measurements on an Elekta Unity. Simulations with Geant4 and the Monaco treatment planning system (TPS), and EBT-3 film measurements, were also performed for comparison. Measured MO Skin ™ entry surface doses, relative to D max , were (9.9 ± 0.2)%, (10.1 ± 0.3)%, (11.3 ± 0.6)%, (12.9 ± 1.0)%, and (13.4 ± 1.0)% for 1 × 1 cm 2 , 3 × 3 cm 2 , 5 × 5 cm 2 , 10 × 10 cm 2 , and 22 × 22 cm 2 fields, respectively. For the investigated fields, the maximum percent differences of Geant4, TPS, and film doses extrapolated and interpolated to a depth suitable for skin dose assessment at the beam entry, relative to MO Skin ™ measurements at an equivalent depth were 1.0%, 2.8%, and 14.3%, respectively, and at a WED of 199.67 mm at the beam exit, 3.2%, 3.7% and 5.7%, respectively. The largest measured increase in exit dose, due to the electron return effect, was 15.4% for the 10 × 10 cm 2 field size using the MO Skin ™ and 17.9% for the 22 × 22 cm 2 field size, using Geant4 calculations. The results presented in the study validate the suitability of the MO Skin ™ detector for transverse MR-linac surface dosimetry.

Stable isotopes and foraging behaviors support the role of antipredator benefits in driving the association between two marine fishes - Christopher R. Haak; Michael Power; Alexander D. M. Wilson; Andy J. Danylchuk (Oecologia, 2023)

Drivers of the microbial metabolic quotient across global grasslands - A. C. Risch; S. Zimmermann; M. Schütz; E. T. Borer; A. A. D. Broadbent; M. C. Caldeira; K. F. Davies; N. Eisenhauer; A. Eskelinen; P. A. Fay; F. Hagedorn; J. M. H. Knops; et al. (Global Ecology and Biogeography, 2023)
Aim The microbial metabolic quotient (MMQ; mg CO 2 ‐C/mg MBC/h), defined as the amount of microbial CO 2 respired (MR; mg CO 2 ‐C/kg soil/h) per unit of microbial biomass C (MBC; mg C/kg soil), is a key parameter for understanding the microbial regulation of the carbon (C) cycle, including soil C sequestration. Here, we experimentally tested hypotheses about the individual and interactive effects of multiple nutrient addition (nitrogen + phosphorus + potassium + micronutrients) and herbivore exclusion on MR, MBC and MMQ across 23 sites (five continents). Our sites encompassed a wide range of edaphoclimatic conditions; thus, we assessed which edaphoclimatic variables affected MMQ the most and how they interacted with our treatments. Location Australia, Asia, Europe, North/South America. Time period 2015–2016. Major taxa Soil microbes. Methods Soils were collected from plots with established experimental treatments. MR was assessed in a 5‐week laboratory incubation without glucose addition, MBC via substrate‐induced respiration. MMQ was calculated as MR/MBC and corrected for soil temperatures (MMQsoil). Using linear mixed effects models (LMMs) and structural equation models (SEMs), we analysed how edaphoclimatic characteristics and treatments interactively affected MMQsoil. Results MMQsoil was higher in locations with higher mean annual temperature, lower water holding capacity and lower soil organic C concentration, but did not respond to our treatments across sites as neither MR nor MBC changed. We attributed this relative homeostasis to our treatments to the modulating influence of edaphoclimatic variables. For example, herbivore exclusion, regardless of fertilization, led to greater MMQsoil only at sites with lower soil organic C ( Main conclusions Our results pinpoint the main variables related to MMQsoil across grasslands and emphasize the importance of the local edaphoclimatic conditions in controlling the response of the C cycle to anthropogenic stressors. By testing hypotheses about MMQsoil across global edaphoclimatic gradients, this work also helps to align the conflicting results of prior studies.

Influence of topical capsaicin cream on thermoregulation and perception during acute exercise in the heat - Alejandro M. Rosales; Marie Powers; Matthias J. Walters; Mark L. McGlynn; Christopher W. Collins; Dustin R. Slivka (Journal of Thermal Biology, 2023)

Cephalopods, a gap in the European Marine Strategy Framework Directive and their future integration - Bianca T. C. Bobowski; Anne Marie Power; Graham J. Pierce; Ana Moreno; Ane Iriondo; Julio Valeiras; Inna M. Sokolova; Daniel Oesterwind (Marine Biology, 2023)
With the aim of maintaining or obtaining good environmental status in the Northeast Atlantic and northern Mediterranean Sea, the European Marine Strategy Framework Directive (EU-MSFD) came into force in 2008. All EU Member States (MS) have the task of assessing the current state of their adjacent waters to guarantee sustainable use of marine resources and healthy ecosystems for the current and future generations. Although the MSFD has been implemented for over a decade, there are still gaps in the assessment of various ecologically and commercially important marine species, such as cephalopods. Here we describe the status of cephalopods, a key component of marine ecosystems and a valuable fishing resource, within the MSFD. To do so, we review how MS deal with this group in their reporting and identify and explain the gaps in the cephalopod assessment. We describe the main challenges including the limited data and the rarity of dedicated surveys on cephalopods. However, we argue that cephalopods can be partially integrated into the EU-MSFD assessment, illustrating the current opportunities and future possibilities of their integration into the MSFD, mainly using Descriptors 1–4. Graphical abstract

The impacts of a global pandemic on the efficacy and stability of contemporary wildlife conservation: South Africa as a case study - David A. Ehlers Smith; Yvette C. Ehlers Smith; Harriet T. Davies-Mostert; Lindy J. Thompson; Daniel M. Parker; Deon de Villiers; Dean Ricketts; Brent Coverdale; Peter J. Roberts; Christopher Kelly; Duncan N. Macfadyen; Nomthandazo S. Manqele; et al. (Ambio, 2023)
Conservationists speculated on potential benefits to wildlife of lockdown restrictions because of the COVID-19 pandemic but voiced concern that restrictions impeded nature conservation. We assessed the effects of lockdown restrictions on biodiversity conservation in South Africa, a biodiverse country with economic inequality and reliance on wildlife resources. We solicited expert opinion using the IUCN’s Threats Classification Scheme to structure a questionnaire and illustrated responses with individual case studies from government parastatal and non-governmental conservation organisations. The most highly reported threats were biological resource use, residential/commercial developments, invasive species, and human intrusions. The trends reported by 90 survey respondents were supported by case studies using environmental compliance data from parastatal conservation organisations. Lack of tourism revenue and funding were cited as hindrances to conservation. Mechanisms to prevent environmental degradation in the face of global emergencies must be implemented and ‘ring-fenced’ to ensure conservation is not a casualty during future global crises.

Two canonically aerobic foraminifera express distinct peroxisomal and mitochondrial metabolisms - Christopher Powers; Fatma Gomaa; Elizabeth B. Billings; Daniel R. Utter; David J. Beaudoin; Virginia P. Edgcomb; Colleen M. Hansel; Scott D. Wankel; Helena L. Filipsson; Ying Zhang; Joan M. Bernhard (Frontiers in Marine Science, 2022)
Certain benthic foraminifera thrive in marine sediments with low or undetectable oxygen. Potential survival avenues used by these supposedly aerobic protists include fermentation and anaerobic respiration, although details on their adaptive mechanisms remain elusive. To better understand the metabolic versatility of foraminifera, we studied two benthic species that thrive in oxygen-depleted marine sediments. Here we detail, via transcriptomics and metatranscriptomics, differential gene expression of Nonionella stella and Bolivina argentea , collected from Santa Barbara Basin, California, USA, in response to varied oxygenation and chemical amendments. Organelle-specific metabolic reconstructions revealed these two species utilize adaptable mitochondrial and peroxisomal metabolism. N. stella , most abundant in anoxia and characterized by lack of food vacuoles and abundance of intracellular lipid droplets, was predicted to couple the putative peroxisomal beta-oxidation and glyoxylate cycle with a versatile electron transport system and a partial TCA cycle. In contrast, B. argentea , most abundant in hypoxia and contains food vacuoles, was predicted to utilize the putative peroxisomal gluconeogenesis and a full TCA cycle but lacks the expression of key beta-oxidation and glyoxylate cycle genes. These metabolic adaptations likely confer ecological success while encountering deoxygenation and expand our understanding of metabolic modifications and interactions between mitochondria and peroxisomes in protists.

Leaf habit affects the distribution of drought sensitivity but not water transport efficiency in the tropics - German Vargas G.; Norbert Kunert; William M. Hammond; Z. Carter Berry; Leland K. Werden; Chris M. Smith‐Martin; Brett T. Wolfe; Laura Toro; Ariadna Mondragón‐Botero; Jesús N. Pinto‐Ledezma; Naomi B. Schwartz; María Uriarte; et al. (Ecology Letters, 2022)
Considering the global intensification of aridity in tropical biomes due to climate change, we need to understand what shapes the distribution of drought sensitivity in tropical plants. We conducted a pantropical data synthesis representing 1117 species to test whether xylem‐specific hydraulic conductivity (K S ), water potential at leaf turgor loss (Ψ TLP ) and water potential at 50% loss of K S (Ψ P50 ) varied along climate gradients. The Ψ TLP and Ψ P50 increased with climatic moisture only for evergreen species, but K S did not. Species with high Ψ TLP and Ψ P50 values were associated with both dry and wet environments. However, drought‐deciduous species showed high Ψ TLP and Ψ P50 values regardless of water availability, whereas evergreen species only in wet environments. All three traits showed a weak phylogenetic signal and a short half‐life. These results suggest strong environmental controls on trait variance, which in turn is modulated by leaf habit along climatic moisture gradients in the tropics.

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

Age, growth and diet of crevalle jack ( Caranx hippos ) in the Gulf of Mexico - Amanda E. Jefferson; Matthew B. Jargowsky; Genevieve M. Ivec; Pearce T. Cooper; Jessica L. Carroll; Carissa L. Gervasi; Jennifer S. Rehage; John F. Mareska; Sean P. Powers; J. Marcus Drymon (Fisheries Management and Ecology, 2022)
The goals of this study were to generate baseline population dynamics parameters for Gulf of Mexico crevalle jack Caranx hippos and examine the foraging habits of Mississippi and Alabama crevalle jack. Specimens were collected from Mississippi, Alabama and Florida, and age was estimated from sagittal otoliths. Stomachs from some specimens were retained for dietary analyses. Age classes spanned 0–20 years. Overall growth was best represented by the logistic growth model, whereas sex‐specific growth was best represented by a version of the von Bertalanffy growth function that allowed L ∞ to vary by sex while holding k and t 0 constant between sexes. Fishes were more important to crevalle jack diet than invertebrates, and diet varied among locations and years. These findings will address fundamental knowledge gaps to inform age‐based stock assessments for crevalle jack and ecosystem approaches to fisheries management in the Gulf of Mexico.

Transmission of Klebsiella strains and plasmids within and between grey‐headed flying fox colonies - Ben Vezina; Louise M. Judd; Fiona K. McDougall; Wayne S. J. Boardman; Michelle L. Power; Jane Hawkey; Sylvain Brisse; Jonathan M. Monk; Kathryn E. Holt; Kelly L. Wyres (Environmental Microbiology, 2022)
Summary The grey‐headed flying fox ( Pteropus poliocephalus ) is an endemic Australian fruit bat, known to carry zoonotic pathogens. We recently showed they harbour bacterial pathogen Klebsiella pneumoniae and closely related species in the K . pneumoniae species complex ( Kp SC); however, the dynamics of Kp SC transmission and gene flow within flying fox colonies are poorly understood. High‐resolution genome comparisons of 39 Kp SC isolates from grey‐headed flying foxes identified five putative strain transmission clusters (four intra‐ and one inter‐colony). The instance of inter‐colony strain transmission of K . africana was found between two flying fox populations within flying distance, indicating either direct or indirect transmission through a common food/water source. All 11 plasmids identified within the Kp SC isolates showed 73% coverage (mean) and ≥95% identity to human‐associated Kp SC plasmids, indicating gene flow between human clinical and grey‐headed flying fox isolates. Along with strain transmission, inter‐species horizontal plasmid transmission between K . pneumoniae and Klebsiella africana was also identified within a flying fox colony. Finally, genome‐scale metabolic models were generated to predict and compare substrate usage to previously published Kp SC models, from human and environmental sources. These models indicated no distinction on the basis of metabolic capabilities. Instead, metabolic capabilities were consistent with population structure and ST/lineage.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The 16th Workshop on Antarctic Meteorology and Climate and 6th Year of Polar Prediction in the Southern Hemisphere Meeting - David H. Bromwich; Matthew A. Lazzara; Arthur M. Cayette; Jordan G. Powers; Kirstin Werner; John J. Cassano; Steven R. Colwell; Scott Carpentier; Xun Zou (Advances in Atmospheric Sciences, 2022)

Reduced Cerebellar Brain Inhibition Measured Using Dual-Site TMS in Older Than in Younger Adults - B. K. Rurak; J. P. Rodrigues; B. D. Power; P. D. Drummond; A. M. Vallence (The Cerebellum, 2022)

Post-traumatic Osteoarthritis in Rabbits Following Traumatic Injury and Surgical Reconstruction of the Knee - Feng Wei; Madeleine J. F. Powers; Gerardo E. Narez; Loic M. Dejardin; Tammy Haut Donahue; Roger C. Haut (Annals of Biomedical Engineering, 2022)

The genetic and ecophysiological diversity of Microcystis - Gregory J. Dick; Melissa B. Duhaime; Jacob T. Evans; Reagan M. Errera; Casey M. Godwin; Jenan J. Kharbush; Helena S. Nitschky; McKenzie A. Powers; Henry A. Vanderploeg; Kathryn C. Schmidt; Derek J. Smith; Colleen E. Yancey; et al. (Environmental Microbiology, 2021)
Summary Microcystis is a cyanobacterium that forms toxic blooms in freshwater ecosystems around the world. Biological variation among taxa within the genus is apparent through genetic and phenotypic differences between strains and via the spatial and temporal distribution of strains in the environment, and this fine‐scale diversity exerts strong influence over bloom toxicity. Yet we do not know how varying traits of Microcystis strains govern their environmental distribution, the tradeoffs and links between these traits, or how they are encoded at the genomic level. Here we synthesize current knowledge on the importance of diversity within Microcystis and on the genes and traits that likely underpin ecological differentiation of taxa. We briefly review spatial and environmental patterns of Microcystis diversity in the field and genetic evidence for cohesive groups within Microcystis . We then compile data on strain‐level diversity regarding growth responses to environmental conditions and explore evidence for variation of community interactions across Microcystis strains. Potential links and tradeoffs between traits are identified and discussed. The resulting picture, while incomplete, highlights key knowledge gaps that need to be filled to enable new models for predicting strain‐level dynamics, which influence the development, toxicity and cosmopolitan nature of Microcystis blooms.

Temporal rarity is a better predictor of local extinction risk than spatial rarity - Peter A. Wilfahrt; Ashley L. Asmus; Eric W. Seabloom; Jeremiah A. Henning; Peter Adler; Carlos A. Arnillas; Jonathan D. Bakker; Lori Biederman; Lars A. Brudvig; Marc Cadotte; Pedro Daleo; Anu Eskelinen; et al. (Ecology, 2021)
Spatial rarity is often used to predict extinction risk, but rarity can also occur temporally. Perhaps more relevant in the context of global change is whether a species is core to a community (persistent) or transient (intermittently present), with transient species often susceptible to human activities that reduce niche space. Using 5–12 yr of data on 1,447 plant species from 49 grasslands on five continents, we show that local abundance and species persistence under ambient conditions are both effective predictors of local extinction risk following experimental exclusion of grazers or addition of nutrients; persistence was a more powerful predictor than local abundance. While perturbations increased the risk of exclusion for low persistence and abundance species, transient but abundant species were also highly likely to be excluded from a perturbed plot relative to ambient conditions. Moreover, low persistence and low abundance species that were not excluded from perturbed plots tended to have a modest increase in abundance following perturbance. Last, even core species with high abundances had large decreases in persistence and increased losses in perturbed plots, threatening the long‐term stability of these grasslands. Our results demonstrate that expanding the concept of rarity to include temporal dynamics, in addition to local abundance, more effectively predicts extinction risk in response to environmental change than either rarity axis predicts alone.

The clinical presentation, treatment and outcome of serologically confirmed paediatric Lyme disease in the Republic of Ireland over a 5-year period: a retrospective cohort study - Karina M. Forde; Joanne O’Gorman; Patrick J. Gavin; Matthew S. Dryden; Deirbhile Keady; Belinda Hanahoe; Colm McDonnell; Lorraine Power; Bartley Cryan; James Sweeney; Karl F. Conyard; Michael J. O’Grady (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Climate‐related geographical variation in performance traits across the invasion front of a widespread non‐native insect - Lily M. Thompson; Sean D. Powers; Ashley Appolon; Petra Hafker; Lelia Milner; Dylan Parry; Salvatore J. Agosta; Kristine L. Grayson (Journal of Biogeography, 2021)
Aim Invasive species are ideal systems for testing geographical differences in performance traits and measuring evolutionary responses as a species spreads across divergent climates and habitats. The European gypsy moth, Lymantria dispar dispar L. (Lepidoptera: Erebidae), is a generalist forest defoliator introduced to Medford, Massachusetts, USA in 1869. The invasion front extends from Minnesota to North Carolina and the ability of this species to adapt to local climate may contribute to its continuing spread. We evaluated the performance of populations along the climatic gradient of the invasion front to test for a relationship between climate and ecologically important performance traits. Location Eastern United States of America Taxon Lymantria dispar dispar L. (Lepidoptera: Erebidae) Methods Insects from 14 populations across the US invasion front and interior of the invasive range were reared from hatch to adult emergence in six constant temperature treatments. The responses of survival, pupal mass and larval development time were analysed as a function of source climate (annual mean normal temperature), rearing temperature and their interaction using multiple polynomial regression. Results With the exception of female development time, there were no significant interactions between source climate and rearing temperature, indicating little divergence in the shape of thermal reaction norms among populations. Source population and rearing temperature were significant predictors of survival and pupal mass. Independent of rearing temperature, populations from warmer climates had lower survival than those from colder climates, but attained larger body size despite similar development times. Larval development time was dependent on rearing temperature, but there were not consistent relationships with source climate. Main Conclusions Thermal adaptation can be an important factor shaping the spread of invasive species, particularly in the context of climate change. Our results suggest that L. d. dispar is highly plastic, but has undergone climate‐related adaptation in thermal performance and life‐history traits as it spread across North America.

Global impacts of fertilization and herbivore removal on soil net nitrogen mineralization are modulated by local climate and soil properties - Anita C. Risch; Stefan Zimmermann; Barbara Moser; Martin Schütz; Frank Hagedorn; Jennifer Firn; Philip A. Fay; Peter B. Adler; Lori A. Biederman; John M. Blair; Elizabeth T. Borer; Arthur A. D. Broadbent; et al. (Global Change Biology, 2020)
Soil nitrogen (N) availability is critical for grassland functioning. However, human activities have increased the supply of biologically limiting nutrients, and changed the density and identity of mammalian herbivores. These anthropogenic changes may alter net soil N mineralization (soil net N min ), that is, the net balance between N mineralization and immobilization, which could severely impact grassland structure and functioning. Yet, to date, little is known about how fertilization and herbivore removal individually, or jointly, affect soil net N min across a wide range of grasslands that vary in soil and climatic properties. Here we collected data from 22 grasslands on five continents, all part of a globally replicated experiment, to assess how fertilization and herbivore removal affected potential (laboratory‐based) and realized (field‐based) soil net N min . Herbivore removal in the absence of fertilization did not alter potential and realized soil net N min . However, fertilization alone and in combination with herbivore removal consistently increased potential soil net N min. Realized soil net N min , in contrast, significantly decreased in fertilized plots where herbivores were removed. Treatment effects on potential and realized soil net N min were contingent on site‐specific soil and climatic properties. Fertilization effects on potential soil net N min were larger at sites with higher mean annual precipitation (MAP) and temperature of the wettest quarter (T.q.wet). Reciprocally, realized soil net N min declined most strongly with fertilization and herbivore removal at sites with lower MAP and higher T.q.wet. In summary, our findings show that anthropogenic nutrient enrichment, herbivore exclusion and alterations in future climatic conditions can negatively impact soil net N min across global grasslands under realistic field conditions. This is an important context‐dependent knowledge for grassland management worldwide.

Microbial processing of plant remains is co‐limited by multiple nutrients in global grasslands - Raúl Ochoa‐Hueso; Elizabeth T. Borer; Eric W. Seabloom; Sarah E. Hobbie; Anita C. Risch; Scott L. Collins; Juan Alberti; Héctor A. Bahamonde; Cynthia S. Brown; Maria C. Caldeira; Pedro Daleo; Chris R. Dickman; et al. (Global Change Biology, 2020)
Microbial processing of aggregate‐unprotected organic matter inputs is key for soil fertility, long‐term ecosystem carbon and nutrient sequestration and sustainable agriculture. We investigated the effects of adding multiple nutrients (nitrogen, phosphorus and potassium plus nine essential macro‐ and micro‐nutrients) on decomposition and biochemical transformation of standard plant materials buried in 21 grasslands from four continents. Addition of multiple nutrients weakly but consistently increased decomposition and biochemical transformation of plant remains during the peak‐season, concurrent with changes in microbial exoenzymatic activity. Higher mean annual precipitation and lower mean annual temperature were the main climatic drivers of higher decomposition rates, while biochemical transformation of plant remains was negatively related to temperature of the wettest quarter. Nutrients enhanced decomposition most at cool, high rainfall sites, indicating that in a warmer and drier future fertilized grassland soils will have an even more limited potential for microbial processing of plant remains.

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

The 13th and 14th Workshops on Antarctic Meteorology and Climate - Matthew A. Lazzara; Sophie A. Orendorf; Taylor P. Norton; Jordan G. Powers; David H. Bromwich; Scott Carpentier; John J. Cassano; Steven R. Colwell; Arthur M. Cayette; Kirstin Werner (Advances in Atmospheric Sciences, 2020)

A catastrophic tropical drought kills hydraulically vulnerable tree species - Jennifer S. Powers; German Vargas G.; Timothy J. Brodribb; Naomi B. Schwartz; Daniel Pérez‐Aviles; Chris M. Smith‐Martin; Justin M. Becknell; Filippo Aureli; Roger Blanco; Erick Calderón‐Morales; Julio C. Calvo‐Alvarado; Ana Julieta Calvo‐Obando; et al. (Global Change Biology, 2020)
Drought‐related tree mortality is now a widespread phenomenon predicted to increase in magnitude with climate change. However, the patterns of which species and trees are most vulnerable to drought, and the underlying mechanisms have remained elusive, in part due to the lack of relevant data and difficulty of predicting the location of catastrophic drought years in advance. We used long‐term demographic records and extensive databases of functional traits and distribution patterns to understand the responses of 20–53 species to an extreme drought in a seasonally dry tropical forest in Costa Rica, which occurred during the 2015 El Niño Southern Oscillation event. Overall, species‐specific mortality rates during the drought ranged from 0% to 34%, and varied little as a function of tree size. By contrast, hydraulic safety margins correlated well with probability of mortality among species, while morphological or leaf economics spectrum traits did not. This firmly suggests hydraulic traits as targets for future research.

Evaluation of Australian Tsunami Warning Thresholds Using Inundation Modelling - Diana J. M. Greenslade; Burak Uslu; Stewart C. R. Allen; Claire L. Kain; Kaya M. Wilson; Hannah E. Power (Pure and Applied Geophysics, 2020)

Effect of Shallow Slip Amplification Uncertainty on Probabilistic Tsunami Hazard Analysis in Subduction Zones: Use of Long-Term Balanced Stochastic Slip Models - A. Scala; S. Lorito; F. Romano; S. Murphy; J. Selva; R. Basili; A. Babeyko; A. Herrero; A. Hoechner; F. Løvholt; F. E. Maesano; P. Perfetti; et al. (Pure and Applied Geophysics, 2020)

Methane Seeps on the US Atlantic Margin and Their Potential Importance to Populations of the Commercially Valuable Deep-Sea Red Crab, Chaceon quinquedens - Phillip J. Turner; Bernard Ball; Zoie Diana; Andrea Fariñas-Bermejo; Ian Grace; Doreen McVeigh; Megan M. Powers; Loïc Van Audenhaege; Svetlana Maslakova; Craig M. Young; Cindy L. Van Dover (Frontiers in Marine Science, 2020)

Defining Sex-Specific Habitat Suitability for a Northern Gulf of Mexico Shark Assemblage - J. M. Drymon; S. Dedman; J. T. Froeschke; E. A. Seubert; A. E. Jefferson; A. M. Kroetz; J. F. Mareska; S. P. Powers (Frontiers in Marine Science, 2020)

The Presence of a High Peak Feature Within Low-Average Shear Stimuli Induces Quiescence in Venous Endothelial Cells - M. Franzoni; D. T. O’Connor; L. Marcar; D. Power; M. A. Moloney; E. G. Kavanagh; R. L. Leask; J. Nolan; P. A. Kiely; M. T. Walsh (Annals of Biomedical Engineering, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Transcutaneous electrical nerve stimulation improves fatigue performance of the treated and contralateral knee extensors - D. G. Behm; E. M. Colwell; G. M. J. Power; H. Ahmadi; A. S. M. Behm; A. Bishop; C. Murph; J. Pike; B. McAssey; K. Fraser; S. Kearley; M. Ryan (European Journal of Applied Physiology, 2019)

Assessing Nearshore Nekton Abundance, Substrate, and Environmental Conditions in the Northern Gulf of Mexico: Are There Differences Among Three Adjacent Coastal Areas and Have There Been Changes over Three Decades (1986–2015)? - Martin T. O’Connell; Mark S. Peterson; Sean P. Powers; Ann M. Uzee-O’Connell; E. John Anderson; J. Read Hendon (Estuaries and Coasts, 2019)

Tiger sharks eat songbirds: reply - J. M. Drymon; K. Feldheim; A. M. V. Fournier; E. A. Seubert; A. E. Jefferson; A. M. Kroetz; S. P. Powers (Ecology, 2019)

Assessing the impact of charr research past, present, and future - Michael J. Hansen; Charles C. Krueger; Andrew M. Muir; Anders Klemetsen; Michael Power (Hydrobiologia, 2019)

Diel activity patterns in overwintering Labrador anadromous Arctic charr - I. M. Mulder; J. B. Dempson; I. A. Fleming; M. Power (Hydrobiologia, 2019)

Influences of environmental variation on anadromous Arctic charr from the Hornaday River, NWT - L. Chavarie; J. D. Reist; M. M. Guzzo; L. Harwood; M. Power (Hydrobiologia, 2019)

Tiger sharks eat songbirds: scavenging a windfall of nutrients from the sky - J. M. Drymon; K. Feldheim; A. M. V. Fournier; E. A. Seubert; A. E. Jefferson; A. M. Kroetz; S. P. Powers (Ecology, 2019)

Comparing total mercury concentrations of northern Dolly Varden, Salvelinus malma malma, in two Canadian Arctic rivers 1986–1988 and 2011–2013 - L. Tran; J. D. Reist; C. P. Gallagher; M. Power (Polar Biology, 2019)

Turbine entrainment and passage of potadromous fish through hydropower dams: Developing conceptual frameworks and metrics for moving beyond turbine passage mortality - Philip M. Harrison; Eduardo G. Martins; Dirk A. Algera; Trina Rytwinski; Brent Mossop; Alf J. Leake; Michael Power; Steven J. Cooke (Fish and Fisheries, 2019)
Potadromous fishes are vulnerable to involuntary entrainment through hydropower turbines. However, turbines can also provide a downstream passage route for potadromous fish. Here, we review evidence for turbine entrainment and passage in potadromous fish, and evaluate the effects of these processes on upstream and downstream populations. We develop conceptual frameworks and metrics to quantify vulnerability to turbine entrainment removals, and to quantify the efficiency of turbines as a downstream passage route. We highlight factors that influence these processes and provide case‐studies demonstrating their applicability. We found that juvenile potadromous fish are being entrained through turbines at rates high enough to impact upstream populations. Given that juvenile passage survival is often high, we argue that turbines provide an important downstream passage route for potadromous fish. We show that entrainment vulnerability is likely a function of interactions between in‐reservoir fish behaviour, habitat configuration and operations and thus not well captured by passage mortality estimates. Similarly, we show that while passage mortality can limit downstream passage efficiency, passage success is also dependent on reservoir and forebay navigation, along with survival and fitness in the downstream river. We advocate for a shift in focus away from estimates of passage mortality and injury, which have previously accounted for the majority of turbine passage research. Instead, we recommend an approach that focusses on quantification of the factors that influence downstream passage efficiency and entrainment vulnerability. Moreover, we highlight the need to better understand the broader scale impacts of these events on upstream and downstream populations.

Whole Genome Sequence Analysis of Burkholderia contaminans FFH2055 Strain Reveals the Presence of Putative β-Lactamases - José J. Degrossi; Cindy Merino; Adela M. Isasmendi; Lorena M. Ibarra; Chelsea Collins; Nicolás E. Bo; Mariana Papalia; Jennifer S. Fernandez; Claudia M. Hernandez; Krisztina M. Papp-Wallace; Robert A. Bonomo; Miryam S. Vazquez; et al. (Current Microbiology, 2019)

Focal Ischaemic Infarcts Expand Faster in Cerebellar Cortex than Cerebral Cortex in a Mouse Photothrombotic Stroke Model - Nagarajesh Gorlamandala; Jasneet Parmar; Amanda J. Craig; John M. Power; Andrew J. Moorhouse; Arun V. Krishnan; Gary D. Housley (Translational Stroke Research, 2018)

Diverse effects of the common hippopotamus on plant communities and soil chemistry - Douglas J. McCauley; Stuart I. Graham; Todd E. Dawson; Mary E. Power; Mordecai Ogada; Wanja D. Nyingi; John M. Githaiga; Judith Nyunja; Lacey F. Hughey; Justin S. Brashares (Oecologia, 2018)

Effects of competition and herbivory over woody seedling growth in a temperate woodland trump the effects of elevated CO2 - L. Collins; M. M. Boer; V. Resco de Dios; S. A. Power; E. R. Bendall; S. Hasegawa; R. Ochoa Hueso; J. Piñeiro Nevado; R. A. Bradstock (Oecologia, 2018)

Socio-environmental consideration of phosphorus flows in the urban sanitation chain of contrasting cities - Geneviève S. Metson; Steve M. Powers; Rebecca L. Hale; Jesse S. Sayles; Gunilla Öberg; Graham K. MacDonald; Yusuke Kuwayama; Nathaniel P. Springer; Anthony J. Weatherley; Kelly L. Hondula; Kristal Jones; Rubel B. Chowdhury; et al. (Regional Environmental Change, 2018)

Trophic niche dynamics of three nearshore benthic predators in The Bahamas - Oliver N. Shipley; Karen J. Murchie; Michael G. Frisk; Owen R. O’Shea; Maggie M. Winchester; Edward J. Brooks; Jessie Pearson; Michael Power (Hydrobiologia, 2018)

Metabolomics of tomato xylem sap during bacterial wilt reveals Ralstonia solanacearum produces abundant putrescine, a metabolite that accelerates wilt disease - Tiffany M. Lowe‐Power; Connor G. Hendrich; Edda von Roepenack‐Lahaye; Bin Li; Dousheng Wu; Raka Mitra; Beth L. Dalsing; Patrizia Ricca; Jacinth Naidoo; David Cook; Amy Jancewicz; Patrick Masson; et al. (Environmental Microbiology, 2018)
Summary Ralstonia solanacearum thrives in plant xylem vessels and causes bacterial wilt disease despite the low nutrient content of xylem sap. We found that R. solanacearum manipulates its host to increase nutrients in tomato xylem sap, enabling it to grow better in sap from infected plants than in sap from healthy plants. Untargeted GC/MS metabolomics identified 22 metabolites enriched in R. solanacearum ‐infected sap. Eight of these could serve as sole carbon or nitrogen sources for R. solanacearum . Putrescine, a polyamine that is not a sole carbon or nitrogen source for R. solanacearum , was enriched 76‐fold to 37 µM in R. solanacearum ‐infected sap. R. solanacearum synthesized putrescine via a SpeC ornithine decarboxylase. A Δ speC mutant required ≥ 15 µM exogenous putrescine to grow and could not grow alone in xylem even when plants were treated with putrescine. However, co‐inoculation with wildtype rescued ΔspeC growth, indicating R. solanacearum produced and exported putrescine to xylem sap. Intriguingly, treating plants with putrescine before inoculation accelerated wilt symptom development and R. solanacearum growth and systemic spread. Xylem putrescine concentration was unchanged in putrescine‐treated plants, so the exogenous putrescine likely accelerated disease indirectly by affecting host physiology. These results indicate that putrescine is a pathogen‐produced virulence metabolite.

Molecular testing of adult Pacific salmon and trout ( Oncorhynchus spp.) for several RNA viruses demonstrates widespread distribution of piscine orthoreovirus in Alaska and Washington - M K Purcell; R L Powers; J Evered; J Kerwin; T R Meyers; B Stewart; J R Winton (Journal of Fish Diseases, 2018)
This research was initiated in conjunction with a systematic, multiagency surveillance effort in the United States (U.S.) in response to reported findings of infectious salmon anaemia virus ( ISAV ) RNA in British Columbia, Canada. In the systematic surveillance study reported in a companion paper, tissues from various salmonids taken from Washington and Alaska were surveyed for ISAV RNA using the U.S.‐approved diagnostic method, and samples were released for use in this present study only after testing negative. Here, we tested a subset of these samples for ISAV RNA with three additional published molecular assays, as well as for RNA from salmonid alphavirus ( SAV ), piscine myocarditis virus ( PMCV ) and piscine orthoreovirus ( PRV ). All samples ( n = 2,252; 121 stock cohorts) tested negative for RNA from ISAV , PMCV , and SAV . In contrast, there were 25 stock cohorts from Washington and Alaska that had one or more individuals test positive for PRV RNA ; prevalence within stocks varied and ranged from 2% to 73%. The overall prevalence of PRV RNA ‐positive individuals across the study was 3.4% (77 of 2,252 fish tested). Findings of PRV RNA were most common in coho ( Oncorhynchus kisutch Walbaum) and Chinook ( O. tshawytscha Walbaum) salmon.

A comparison of the trophic ecology of Beaufort Sea Gadidae using fatty acids and stable isotopes - J. D. Brewster; C. Giraldo; E. S. Choy; S. A. MacPhee; C. Hoover; B. Lynn; D. G. McNicholl; A. Majewski; B. Rosenberg; M. Power; J. D. Reist; L. L. Loseto (Polar Biology, 2018)

Daily temperature experience and selection by adfluvial bull trout (Salvelinus confluentus) - L. F. G. Gutowsky; P. M. Harrison; E. G. Martins; A. Leake; D. A. Patterson; D. Z. Zhu; M. Power; S. J. Cooke (Environmental Biology of Fishes, 2017)

Comparative Dietary Diversity and Trophic Ecology of Two Estuarine Mesopredators - Andrea M. Kroetz; J. Marcus Drymon; Sean P. Powers (Estuaries and Coasts, 2017)

Individual isotopic specializations predict subsequent inter‐individual variation in movement in a freshwater fish - P. M. Harrison; L. F. G. Gutowsky; E. G. Martins; T. D. Ward; D. A. Patterson; S. J. Cooke; M. Power (Ecology, 2017)
Despite many similarities and intuitive links between individual dietary specialization and behavioral inter‐individual variation, these phenomena have been studied in isolation, and empirical data confirming relationships between these intraspecific variance sources are lacking. Here we use stable isotope analysis and acoustic telemetry to test the hypothesis that individual specialization in trophic (δ 15 N) and littoral/pelagic prey reliance (δ 13 C) covary with inter‐individual variation in movement in a group of 34 free‐swimming burbot ( Lota lota ). By performing stable isotope analysis on tissues with differing isotopic turnover rates (anal fin and dorsal muscle), in 24 lethally sampled burbot, we demonstrate that individual specialization in trophic niche (δ 15 N) and littoral/pelagic prey reliance (δ 13 C) occurred within the population. By performing stable isotope analysis on anal fins of a group of telemetry tagged burbot, we were able to show that interactions between trophic niche and littoral/pelagic prey reliance, explained a significant proportion of the subsequent between‐individual variance in mean movement rates. These findings demonstrate an empirical connection between behavioral inter‐individual variation and dietary specialization, thus providing a substantial expansion of our understanding of the wider ecological consequences of these interesting phenomena.

cis-Jasmone Elicits Aphid-Induced Stress Signalling in Potatoes - Islam S. Sobhy; Christine M. Woodcock; Stephen J. Powers; John C. Caulfield; John A. Pickett; Michael A. Birkett (Journal of Chemical Ecology, 2017)

Ecology under lake ice - Stephanie E. Hampton; Aaron W. E. Galloway; Stephen M. Powers; Ted Ozersky; Kara H. Woo; Ryan D. Batt; Stephanie G. Labou; Catherine M. O'Reilly; Sapna Sharma; Noah R. Lottig; Emily H. Stanley; Rebecca L. North; et al. (Ecology Letters, 2017)
Winter conditions are rapidly changing in temperate ecosystems, particularly for those that experience periods of snow and ice cover. Relatively little is known of winter ecology in these systems, due to a historical research focus on summer ‘growing seasons’. We executed the first global quantitative synthesis on under‐ice lake ecology, including 36 abiotic and biotic variables from 42 research groups and 101 lakes, examining seasonal differences and connections as well as how seasonal differences vary with geophysical factors. Plankton were more abundant under ice than expected; mean winter values were 43.2% of summer values for chlorophyll a , 15.8% of summer phytoplankton biovolume and 25.3% of summer zooplankton density. Dissolved nitrogen concentrations were typically higher during winter, and these differences were exaggerated in smaller lakes. Lake size also influenced winter‐summer patterns for dissolved organic carbon ( DOC ), with higher winter DOC in smaller lakes. At coarse levels of taxonomic aggregation, phytoplankton and zooplankton community composition showed few systematic differences between seasons, although literature suggests that seasonal differences are frequently lake‐specific, species‐specific, or occur at the level of functional group. Within the subset of lakes that had longer time series, winter influenced the subsequent summer for some nutrient variables and zooplankton biomass.

Probabilistic Hazard of Tsunamis Generated by Submarine Landslides in the Cook Strait Canyon (New Zealand) - Emily M. Lane; Joshu J. Mountjoy; William L. Power; Christof Mueller (Pure and Applied Geophysics, 2016)

Northern Dolly Varden charr total mercury concentrations: variation by life-history type - L. Tran; J. D. Reist; M. Power (Hydrobiologia, 2016)

Attentional function and basal forebrain cholinergic neuron morphology during aging in the Ts65Dn mouse model of Down syndrome - Brian E. Powers; Ramon Velazquez; Christy M. Kelley; Jessica A. Ash; Myla S. Strawderman; Melissa J. Alldred; Stephen D. Ginsberg; Elliott J. Mufson; Barbara J. Strupp (Brain Structure and Function, 2016)

Burbot and large hydropower in North America: benefits, threats and research needs for mitigation - P. M. Harrison; L. F. G. Gutowsky; E. G. Martins; D. A. Patterson; S. J. Cooke; M. Power (Fisheries Management and Ecology, 2016)
In North America, burbot Lota lota (L.), interactions with hydropower are common, southern burbot populations are endangered and hydropower has been implicated in the decline. Thus, the objectives of this review were to identify threats and benefits of hydropower to riverine and reservoir dwelling burbot, assess overall impacts and identify key research needs for mitigation. Review findings suggest that while winter hydropower discharge regimes threaten riverine burbot spawning, burbot often successfully exploit reservoir environments. Further, while turbine entrainment has been hypothesised as a factor in the decline of burbot populations, low adult vulnerability to passage and a high resilience to juvenile removals likely mean risk to populations is low. Identified research needs include better definitions of flow and temperature requirements for riverine burbot and a quantification of the potential for reservoirs to act as source populations for downstream impacted zones. This review highlights the Pacific watershed focus of existing work and calls for status assessments and ecological research of burbot in North American Arctic and Atlantic watersheds where large hydropower and burbot interactions are common yet rarely studied.

Temporal plasticity in thermal‐habitat selection of burbot Lota lota a diel‐migrating winter‐specialist - P. M. Harrison; L. F. G. Gutowsky; E. G. Martins; D. A. Patterson; S. J. Cooke; M. Power (Journal of Fish Biology, 2016)
In this study, animal‐borne telemetry with temperature sensors was coupled with extensive habitat temperature monitoring in a dimictic reservoir, to test the following hypotheses: behavioural thermoregulation occurs throughout the year and temperature selection varies on a diel and seasonal basis, in a winter‐specialist diel‐migrating fish. Burbot Lota lota demonstrated nightly behavioural thermoregulation throughout the year, with a large seasonal shift between selection for very cold temperatures ( L. lota avoided habitats warmer than optimal for reproduction and feeding during the spawning and non‐reproductive periods, respectively, active selection was limited to selection for 4–6° C habitat during the prespawning period. Although behavioural thermoregulation explained the night‐time migration, behavioural thermoregulation only partially explained daytime behaviour, indicating that diel migration is best explained by a combination of factors. Thus, thermal‐habitat selection was a good predictor of night‐time habitat occupancy in a diel‐migrating species. Together, these results show that thermal‐habitat selection by fishes may be important throughout the year and a more seasonally plastic behaviour than previously recognized.

The 10th Antarctic meteorological observation, modeling, and forecasting workshop - Steve R. Colwell; Arthur M. Cayette; Matthew A. Lazzara; Jordan G. Powers; David H. Bromwich; John J. Cassano; Scott Carpentier (Advances in Atmospheric Sciences, 2016)

A moving target—incorporating knowledge of the spatial ecology of fish into the assessment and management of freshwater fish populations - Steven J. Cooke; Eduardo G. Martins; Daniel P. Struthers; Lee F. G. Gutowsky; Michael Power; Susan E. Doka; John M. Dettmers; David A. Crook; Martyn C. Lucas; Christopher M. Holbrook; Charles C. Krueger (Environmental Monitoring and Assessment, 2016)

Interactions between Bacteria And Aspen Defense Chemicals at the Phyllosphere – Herbivore Interface - Charles J. Mason; Tiffany M. Lowe-Power; Kennedy F. Rubert-Nason; Richard L. Lindroth; Kenneth F. Raffa (Journal of Chemical Ecology, 2016)

Shifting grassland plant community structure drives positive interactive effects of warming and diversity on aboveground net primary productivity - Jane M. Cowles; Peter D. Wragg; Alexandra J. Wright; Jennifer S. Powers; David Tilman (Global Change Biology, 2016)
Ecosystems worldwide are increasingly impacted by multiple drivers of environmental change, including climate warming and loss of biodiversity. We show, using a long‐term factorial experiment, that plant diversity loss alters the effects of warming on productivity. Aboveground primary productivity was increased by both high plant diversity and warming, and, in concert, warming (≈1.5 °C average above and belowground warming over the growing season) and diversity caused a greater than additive increase in aboveground productivity. The aboveground warming effects increased over time, particularly at higher levels of diversity, perhaps because of warming‐induced increases in legume and C4 bunch grass abundances, and facilitative feedbacks of these species on productivity. Moreover, higher plant diversity was associated with the amelioration of warming‐induced environmental conditions. This led to cooler temperatures, decreased vapor pressure deficit, and increased surface soil moisture in higher diversity communities. Root biomass (0–30 cm) was likewise consistently greater at higher plant diversity and was greater with warming in monocultures and at intermediate diversity, but at high diversity warming had no detectable effect. This may be because warming increased the abundance of legumes, which have lower root : shoot ratios than the other types of plants. In addition, legumes increase soil nitrogen (N) supply, which could make N less limiting to other species and potentially decrease their investment in roots. The negative warming × diversity interaction on root mass led to an overall negative interactive effect of these two global change factors on the sum of above and belowground biomass, and thus likely on total plant carbon stores. In total, plant diversity increased the effect of warming on aboveground net productivity and moderated the effect on root mass. These divergent effects suggest that warming and changes in plant diversity are likely to have both interactive and divergent impacts on various aspects of ecosystem functioning.

An analysis of P seudomonas genomic diversity in take‐all infected wheat fields reveals the lasting impact of wheat cultivars on the soil microbiota - T. H. Mauchline; D. Chedom‐Fotso; G. Chandra; T. Samuels; N. Greenaway; A. Backhaus; V. McMillan; G. Canning; S. J. Powers; K. E. Hammond‐Kosack; P. R. Hirsch; I. M. Clark; et al. (Environmental Microbiology, 2015)
Summary Manipulation of the soil microbiota associated with crop plants has huge promise for the control of crop pathogens. However, to fully realize this potential we need a better understanding of the relationship between the soil environment and the genes and phenotypes that enable microbes to colonize plants and contribute to biocontrol. A recent 2 years of investigation into the effect of wheat variety on second year crop yield in the context of take‐all fungal infection presented the opportunity to examine soil microbiomes under closely defined field conditions. Amplicon sequencing of second year soil samples showed that P seudomonas spp. were particularly affected by the wheat cultivar grown in year one. Consequently, 318 rhizosphere‐associated P seudomonas fluorescens strains were isolated and characterized across a variety of genetic and phenotypic traits. Again, the wheat variety grown in the first year of the study was shown to exert considerable selective pressure on both the extent and nature of P seudomonas genomic diversity. Furthermore, multiple significant correlations were identified within the phenotypic/genetic structure of the Pseudomonas population, and between individual genotypes and the external wheat field environment. The approach outlined here has considerable future potential for our understanding of plant–microbe interactions, and for the broader analysis of complex microbial communities.

Fish community dynamics following dam removal in a fragmented agricultural stream - Matthew S. Kornis; Brian C. Weidel; Stephen M. Powers; Matthew W. Diebel; Timothy J. Cline; Justin M. Fox; James F. Kitchell (Aquatic Sciences, 2015)

Data dialogues: critical connections for designing and implementing future nanomaterial research - Christina M. Powers; Khara D. Grieger; Christian Beaudrie; Christine Ogilvie Hendren; J. Michael Davis; Amy Wang; Christie M. Sayes; Margaret MacDonell; Jeffrey S. Gift (Environment Systems and Decisions, 2015)

Genetic diversity, population structure and phenotypic variation in European Salix viminalis L. (Salicaceae) - S. Berlin; S. O. Trybush; J. Fogelqvist; N. Gyllenstrand; H. R. Hallingbäck; I. Åhman; N-E. Nordh; I. Shield; S. J. Powers; M. Weih; U. Lagercrantz; A-C. Rönnberg-Wästljung; et al. (Tree Genetics & Genomes, 2014)

The Role of Nitrogen Deposition in Widespread Plant Community Change Across Semi-natural Habitats - Chris D. Field; Nancy B. Dise; Richard J. Payne; Andrea J. Britton; Bridget A. Emmett; Rachel C. Helliwell; Steve Hughes; Laurence Jones; Steven Lees; Jonathan R. Leake; Ian D. Leith; Gareth K. Phoenix; et al. (Ecosystems, 2014)

A new index for variations in the position of the South Pacific convergence zone 1910/11–2011/2012 - M. J. Salinger; Simon McGree; Florent Beucher; Scott B. Power; François Delage (Climate Dynamics, 2014)

Characterization of the DYX2 locus on chromosome 6p22 with reading disability, language impairment, and IQ - John D. Eicher; Natalie R. Powers; Laura L. Miller; Kathryn L. Mueller; Sara Mascheretti; Cecilia Marino; Erik G. Willcutt; John C. DeFries; Richard K. Olson; Shelley D. Smith; Bruce F. Pennington; J. Bruce Tomblin; et al. (Human Genetics, 2014)

Multivariate analysis of MLH1 c.1664T>C (p.Leu555Pro) mismatch repair gene variant demonstrates its pathogenicity - M. P. Farrell; D. J. Hughes; M. Drost; A. J. Wallace; R. J. Cummins; T. A. Fletcher; M. A. Meany; E. W. Kay; N. de Wind; D. G. Power; E. J. Andrews; A. J. Green; et al. (Familial Cancer, 2013)

Head Impact Exposure in Youth Football: High School Ages 14 to 18 Years and Cumulative Impact Analysis - Jillian E. Urban; Elizabeth M. Davenport; Adam J. Golman; Joseph A. Maldjian; Christopher T. Whitlow; Alexander K. Powers; Joel D. Stitzel (Annals of Biomedical Engineering, 2013)

Ontogenetic shifts in morphology and resource use of cisco Coregonus artedi - A. M. Muir; P. Vecsei; T. C. Pratt; C. C. Krueger; M. Power; J. D. Reist (Journal of Fish Biology, 2013)
Two previously described lacustrine cisco Coregonus spp. morphs [ i.e . a small ( L F ), low‐gillraker (≤44) morph and a large (≥300 mm L F ), high‐gillraker (≥45) morph] from Great Slave Lake, NT , Canada, were found to be synonymous with cisco Coregonus artedi. Geometric body shape did not differ between the two size classes nor could they be differentiated by 24 size‐corrected linear measurements, indicating that the two groups had similar phenotypes. Strong, positive correlations between all linear characters and geometric centroid size (a composite variable of fish body length, mass and age) suggested that body morphology changed with age as fish grew. Total gillraker number ( N GR ) increased with L F according to: N GR = 36·3 + 0·034 L F . Differences in gillraker number and phenotype with age and size were explained by shifts in habitat and trophic resource use. Relative abundance within 0–30, 30–60, 60–90 and >90 m depth strata differed between size classes suggesting that morphology changed when fish shifted their habitat as they grew older. Large C. artedi had lower δ 13 C and slightly higher δ 15 N, indicating greater reliance on pelagic prey resources ( i.e . more or larger zooplankton, such as Mysis spp.), compared to small C. artedi , which relied slightly more on benthic prey. Gillraker shape and number have always been used as key diagnostic characters in coregonine taxonomy; based on the findings presented here, ontogenetic shifts should be accounted for in resulting classifications.

Effects of an exercise and hypocaloric healthy eating program on biomarkers associated with long-term prognosis after early-stage breast cancer: a randomized controlled trial - E. Scott; A. J. Daley; H. Doll; N. Woodroofe; R. E. Coleman; N. Mutrie; H. Crank; H. J. Powers; J. M. Saxton (Cancer Causes & Control, 2013)

Current evidence for human yersiniosis in Ireland - T. Ringwood; B. P. Murphy; N. Drummond; J. F. Buckley; A. P. Coveney; H. P. Redmond; J. P. Power; S. Fanning; M. B. Prentice (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Spring climate and summer otolith growth in juvenile Arctic charr, Salvelinus alpinus - J. A. Godiksen; R. Borgstrøm; J. B. Dempson; J. Kohler; H. Nordeng; M. Power; A. Stien; M.-A. Svenning (Environmental Biology of Fishes, 2012)

Engineering gibberellin metabolism in Solanum nigrum L. by ectopic expression of gibberellin oxidase genes - A. Bhattacharya; D. A. Ward; P. Hedden; A. L. Phillips; J. B. Power; M. R. Davey (Plant Cell Reports, 2012)

Impacts of atmospheric nitrogen deposition: responses of multiple plant and soil parameters across contrasting ecosystems in long‐term field experiments - Gareth K. Phoenix; Bridget A. Emmett; Andrea J. Britton; Simon J. M. Caporn; Nancy B. Dise; Rachel Helliwell; Laurence Jones; Jonathan R. Leake; Ian D. Leith; Lucy J. Sheppard; Alwyn Sowerby; Michael G. Pilkington; et al. (Global Change Biology, 2012)
Atmospheric nitrogen ( N ) deposition is a global and increasing threat to biodiversity and ecosystem function. Much of our current understanding of N deposition impacts comes from field manipulation studies, although interpretation may need caution where simulations of N deposition (in terms of dose, application rate and N form) have limited realism. Here, we review responses to simulated N deposition from the UKREATE network, a group of nine experimental sites across the UK in a diversity of heathland, grassland, bog and dune ecosystems which include studies with a high level of realism and where many are also the longest running globally on their ecosystem type. Clear responses were seen across the sites with the greatest sensitivity shown in cover and species richness of bryophytes and lichens. Productivity was also increased at sites where N was the limiting nutrient, while flowering also showed high sensitivity, with increases and declines seen in dominant shrub and forb species, respectively. Critically, these parameters were responsive to some of the lowest additional loadings of N (7.7–10 kg ha −1 yr −1 ) showing potential for impacts by deposition rates seen in even remote and ‘unpolluted’ regions of E urope. Other parameters were less sensitive, but nevertheless showed response to higher doses. These included increases in soil % N and ‘plant available’ KCl extractable N , N cycling rates and acid–base status. Furthermore, an analysis of accumulated dose that quantified response against the total N input over time suggested that N impacts can ‘build up’ within an ecosystem such that even relatively low N deposition rates can result in ecological responses if continued for long enough. Given the responses have important implications for ecosystem structure, function, and recovery from N loading, the clear evidence for impacts at relatively low N deposition rates across a wide range of habitats is of considerable concern.

Source of Selenium Supplementation Influences Testis Selenium Content and Gene Expression Profiles in Single Comb White Leghorn Roosters - Kristen M. Brennan; James L. Pierce; Austin H. Cantor; Anthony J. Pescatore; Rijin Xiao; Ronan F. Power (Biological Trace Element Research, 2012)

Non-cancer endpoints in BRCA1/2 carriers after risk-reducing salpingo-oophorectomy - J. V. Cohen; L. Chiel; L. Boghossian; M. Jones; J. E. Stopfer; J. Powers; T. R. Rebbeck; K. L. Nathanson; S. M. Domchek (Familial Cancer, 2012)

Red snapper management in the Gulf of Mexico: science- or faith-based? - J. H. Cowan; C. B. Grimes; W. F. Patterson; C. J. Walters; A. C. Jones; W. J. Lindberg; D. J. Sheehy; W. E. Pine; J. E. Powers; M. D. Campbell; K. C. Lindeman; S. L. Diamond; et al. (Reviews in Fish Biology and Fisheries, 2011)

Stable isotope-based determinations of the average temperatures experienced by young-of-the-year Svalbard Arctic charr (Salvelinus alpinus (L.)) - J. A. Godiksen; M.-A. Svenning; R. N. Sinnatamby; J. B. Dempson; R. Borgstrøm; M. Power (Polar Biology, 2011)

Epidemiology of non-multiresistant methicillin-resistant Staphylococcus aureus infection in Queensland, Australia: associations with indigenous populations and Panton–Valentine leukocidin - G. R. Nimmo; J. M. Schooneveldt; J. L. Sutherland; S. Power; D. Olesen; C. Selvey; F. Beard; M. Jones; D. L. Paterson (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Relative importance of human activities and climate driving common murre population trends in the Northwest Atlantic - Paul M. Regular; Gregory J. Robertson; William A. Montevecchi; Fyzee Shuhood; Tony Power; Douglas Ballam; John F. Piatt (Polar Biology, 2010)

Latitudinal variation in growth among Arctic charr in eastern North America: evidence for countergradient variation? - Louise Chavarie; J. Brian Dempson; C. J. Schwarz; J. D. Reist; G. Power; M. Power (Hydrobiologia, 2010)

High frequency direct plant regeneration from leaf and petals of Cape Primrose (Streptocarpus) - A. Chaudhury; J. B. Power; M. R. Davey (Journal of Crop Science and Biotechnology, 2010)

Tyrosine hydroxylase, chromogranin A, and steroidogenic acute regulator as markers for successful separation of human adrenal medulla - Stephanie M. J. Fliedner; Jan Breza; Richard Kvetnansky; James F. Powers; Arthur S. Tischler; Robert Wesley; Maria Merino; Hendrik Lehnert; Karel Pacak (Cell and Tissue Research, 2010)

Ultrasequencing of the meiofaunal biosphere: practice, pitfalls and promises - S. CREER; V. G. FONSECA; D. L. PORAZINSKA; R. M. GIBLIN‐DAVIS; W. SUNG; D. M. POWER; M. PACKER; G. R. CARVALHO; M. L. BLAXTER; P. J. D. LAMBSHEAD; W. K. THOMAS (Molecular Ecology, 2010)
Biodiversity assessment is the key to understanding the relationship between biodiversity and ecosystem functioning, but there is a well‐acknowledged biodiversity identification gap related to eukaryotic meiofaunal organisms. Meiofaunal identification is confounded by the small size of taxa, morphological convergence and intraspecific variation. However, the most important restricting factor in meiofaunal ecological research is the mismatch between diversity and the number of taxonomists that are able to simultaneously identify and catalogue meiofaunal diversity. Accordingly, a molecular operational taxonomic unit (MOTU)‐based approach has been advocated for en mass meiofaunal biodiversity assessment, but it has been restricted by the lack of throughput afforded by chain termination sequencing. Contemporary pyrosequencing offers a solution to this problem in the form of environmental metagenetic analyses, but this represents a novel field of biodiversity assessment. Here, we provide an overview of meiofaunal metagenetic analyses, ranging from sample preservation and DNA extraction to PCR, sequencing and the bioinformatic interrogation of multiple, independent samples using 454 Roche sequencing platforms. We report two examples of environmental metagenetic nuclear small subunit 18S (nSSU) analyses of marine and tropical rainforest habitats and provide critical appraisals of the level of putative recombinant DNA molecules (chimeras) in metagenetic data sets. Following stringent quality control measures, environmental metagenetic analyses achieve MOTU formation across the eukaryote domain of life at a fraction of the time and cost of traditional approaches. The effectiveness of Roche 454 sequencing brings substantial advantages to studies aiming to elucidate the molecular genetic richness of not only meiofaunal, but also all complex eukaryotic communities.

Murres, capelin and ocean climate: inter-annual associations across a decadal shift - P. M. Regular; F. Shuhood; T. Power; W. A. Montevecchi; G. J. Robertson; D. Ballam; J. F. Piatt; B. Nakashima (Environmental Monitoring and Assessment, 2009)

Phylogeography and sympatric differentiation of the Arctic charr Salvelinus alpinus (L.) complex in Siberia as revealed by mtDNA sequence analysis - S. S. Alekseyev; R. Bajno; N. V. Gordeeva; J. D. Reist; M. Power; A. F. Kirillov; V. P. Samusenok; A. N. Matveev (Journal of Fish Biology, 2009)
Sequence variation in the mtDNA control region of Arctic charr Salvelinus alpinus and Dolly Varden Salvelinus malma from 56 Siberian and North American populations was analysed to assess their phylogeographic relationships and the origins of sympatric forms. Phylogenetic trees confirm the integrity of phylogroups reported in previous mtDNA studies except that the Siberian group does not separate as a single cluster. Haplotype network analysis indicates the proximity of Siberian and Atlantic haplotypes. These are considered as one Eurasian group represented by the Atlantic, east Siberian (interior Siberia including Transbaikalia, Taimyr) and Eurosiberian (Finland, Spitsbergen, Taimyr) sub‐groups. Salvelinus alpinus with presumably introgressed Bering group (malma) haplotypes were found along eastern Siberian coasts up to the Olenek Bay and the Lena Delta region, where they overlap with the Eurasian group and in the easternmost interior region. It is proposed that Siberia was colonized by S. alpinus in two stages: from the west by the Eurasian group and later from the east by the Bering group. The high diversity of Eurasian group haplotypes in Siberia indicates its earlier colonization by S. alpinus as compared with the European Alps. This colonization was rapid, proceeded from a diverse gene pool, and was followed by differential survival of ancestral mtDNA lineages in different basins and regions, and local mutational events in isolated populations. The results presented here support a northern origin of Transbaikalian S. alpinus , the dispersion of S. alpinus to the Lake Baikal Basin from the Lena Basin, segregation of S. alpinus between Lena tributaries and their restricted migration over the divides between sub‐basins. These results also support sympatric origin of intralacustrine forms of S. alpinus .

Absence of Ross River virus amongst Common brushtail possums (Trichosurus vulpecula) from metropolitan Sydney, Australia - Nichola J. Hill; Michelle L. Power; Elizabeth M. Deane (European Journal of Wildlife Research, 2009)

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Over-expression of a gibberellin 2-oxidase gene from Phaseolus coccineus L. enhances gibberellin inactivation and induces dwarfism in Solanum species - C. Dijkstra; E. Adams; A. Bhattacharya; A. F. Page; P. Anthony; S. Kourmpetli; J. B. Power; K. C. Lowe; S. G. Thomas; P. Hedden; A. L. Phillips; M. R. Davey (Plant Cell Reports, 2008)

Occurrence of Cryptosporidium parvum and Bacterial Pathogens in Faecal Material in the Red Fox (Vulpes vulpes) Population - Y. Nagano; M. B. Finn; C. J. Lowery; T. Murphy; J. Moriarty; E. Power; D. Toolan; A. O’Loughlin; M. Watabe; K. A. McCorry; E. Crothers; J. S. G. Dooley; et al. (Veterinary Research Communications, 2007)

An assessment of de‐calcification procedures for δ 13 C and δ 15 N analysis of yellow perch, walleye and Atlantic salmon scales - R. N. Sinnatamby; J. E. Bowman; J. B. Dempson; M. Power (Journal of Fish Biology, 2007)
The scales of three species of fishes, yellow perch Perca flavescens , walleye Sander vitreus and Atlantic salmon Salmo salar , were acidified and the isotopic signatures were compared to non‐acidified scales from the same fishes. No significant acidification effects on either carbon or nitrogen isotope signatures were found. Results contrast with earlier literature findings noting significant acidification effects and suggest acidification tests be undertaken before scales are used for temporal reconstruction of fish food web positions.

NeuroAIDS, Drug Abuse, and Inflammation: Building Collaborative Research Activities - Joan W. Berman; Monica J. Carson; Linda Chang; Brian M. Cox; Howard S. Fox; R. Gilberto Gonzalez; Glen R. Hanson; Kurt F. Hauser; Wen-Zhe Ho; Jau-Shyong Hong; Eugene O. Major; William F. Maragos; et al. (Journal of Neuroimmune Pharmacology, 2006)

The effects of preservation on fish tissue stable isotope signatures - B. Kelly; J. B. Dempson; M. Power (Journal of Fish Biology, 2006)
The effects of formalin and ethanol preservation on the δ 13 C and δ 15 N isotope signatures of Arctic charr Salvelinus alpinus muscle tissue were examined. The lipid content of the tissue samples studied ranged from 3·6 to 6·1% and was not correlated with the magnitude of observed isotopic shifts in preserved samples. Ethanol and formalin significantly depleted and enriched, respectively, the δ 13 C isotope signatures of preserved tissues when compared to control samples. Ethanol did not significantly enrich δ 15 N signatures in comparison to controls, whereas formalin did. A meta‐analysis of multiple species effects further demonstrated significant preservation effects in fish tissue. Statistical analysis of data obtained by correcting preserved tissue isotope signatures with literature, bootstrapped or meta‐analysis derived correction factors demonstrated significant differences between corrected and control sample isotope signatures or failure to produce a unity slope when the data sets were regressed against one another. Species‐specific, bootstrapped linear correction models resulted in no such errors. Results suggest that species‐specific correction methods should be used for fishes because of the known wide variation in fish tissue lipid content and composition. Accordingly, the use of pilot studies will be required to develop correction factors that properly adjust for preservation effects when interpreting temporal patterns in historic analyses of food webs.

Comparative field performance over 3 years and two sites of transgenic wheat lines expressing HMW subunit transgenes - Peter R. Shewry; Stephen Powers; J. Michael Field; Roger J. Fido; Huw D. Jones; Gillian M. Arnold; Jevon West; Paul A. Lazzeri; Pilar Barcelo; Francisco Barro; Arthur S. Tatham; Frank Bekes; et al. (Theoretical and Applied Genetics, 2006)

Ligand binding and signalling pathways of PTH receptors in sea bream (Sparus auratus) enterocytes - J. Rotllant; P. M. Guerreiro; B. Redruello; H. Fernandes; L. Apolónia; L. Anjos; A. V. M. Canario; D. M. Power (Cell and Tissue Research, 2006)

Latitudinal variation in fecundity among Arctic charr populations in eastern North America - M. Power; J. B. Dempson; J. D. Reist; C. J. Schwarz; G. Power (Journal of Fish Biology, 2005)
Variation in fecundity was examined from 32 populations of Arctic charr Salvelinus alpinus in eastern North America covering a range of 37° latitude and extending from Maine, U.S.A., to northern Ellesmere Island in the Canadian Arctic. Populations were classed as dwarf, normal or anadromous and covered a suite of different habitat and climatic regimes. Fecundity varied with fork length ( L F ), with L F adjusted fecundity differing significantly among populations within each of the morphotypes implying that fecundity was a continuously responsive trait influenced by local environmental factors. Latitudinal variation in fecundity was also evident among morphotypes when the simultaneous effects of both latitude and L F were controlled. There was a significant trade‐off between fecundity and egg size in two of five populations of anadromous Arctic charr, but no evidence in limited data from either normal or dwarf populations. In contrast with some other studies of fecundity in salmonids, there was no evidence for a latitudinal cline in egg size.

Biological effects-based sediment quality in ecological risk assessment for European waters - Pieter J. den Besten; Eric de Deckere; Marc P. Babut; Beth Power; T. Angel DelValls; Christina Zago; Amy M. P. Oen; Susanne Heise (Journal of Soils and Sediments, 2003)

A conceptual model of the Mount Spurr magmatic system from seismic and geochemical observations of the 1992 Crater Peak eruption sequence - Power J.; Jolly A.; Nye C.; Harbin M. (Bulletin of Volcanology, 2002)

Using stable isotopes to confirm the trophic ecology of Arctic charr morphotypes from Lake Hazen, Nunavut, Canada - K. R. R. A. Guiguer; J. D. Reist; M. Power; J. A. Babaluk (Journal of Fish Biology, 2002)
Stable isotopes of carbon and nitrogen were used to examine differences in the feeding ecology of sympatric morphotypes of Arctic charr Sahelinus alpinus from Lake Hazen, Ellesmere Island, in the Canadian High Arctic. Large and small morphotypes possessed significantly different carbon and nitrogen signatures with large‐form Arctic charr being more depleted in 13 C and more enriched in 15 N than the small‐form. Isotope and stomach content analyses yielded consistent results and indicated short‐ and long‐term reliance on fish as a food for large Arctic charr. Large‐form individuals predate on juveniles but do not predate on small‐form individuals ≥ 250 mm. The observed cannibalism by large‐form individuals, therefore, does not act to maintain the bimodal length‐frequency distribution in Lake Hazen. Bimodality is argued to arise for ecological reasons connected with differing habitat use by the morphotypes and the associated differences in resource consumption opportunities.

STOIC: a study of coupled model climatology and variability in tropical ocean regions - Davey M.; Huddleston M.; Sperber K.; Braconnot P.; Bryan F.; Chen D.; Colman R.; Cooper C.; Cubasch U.; Delecluse P.; DeWitt D.; Fairhead L.; et al. (Climate Dynamics, 2002)

Neurovirulence depends on virus input titer in brain in feline immunodeficiency virus infection: Evidence for activation of innate immunity and neuronal injury - J. B. Johnston; C Silva; T Hiebert; R Buist; M. R. Dawood; J Peeling; C Power (Journal of NeuroVirology, 2002)

Molecular systematics of Solanum section Lycopersicum (Lycopersicon) using the nuclear ITS rDNA region - J. A. Marshall; S. Knapp; M. R. Davey; J. B. Power; E. C. Cocking; M. D. Bennett; A. V. Cox (Theoretical and Applied Genetics, 2001)

ENSIP: the El Niño simulation intercomparison project - M. Latif; K. Sperber; J. Arblaster; P. Braconnot; D. Chen; A. Colman; U. Cubasch; C. Cooper; P. Delecluse; D. Dewitt; L. Fairhead; G. Flato; et al. (Climate Dynamics, 2001)

A simple and rapid procedure to establish embryogenic cell suspensions as a source of protoplasts for efficient plant regeneration from two Chinese commercial rice cultivars - K. Tang; X. Sun; D. An; J. B. Power; E. C. Cocking; M. R. Davey (Plant Cell, Tissue and Organ Culture (PCTOC), 2001)

Genetic transformation of wheat: progress during the 1990s into the Millennium - Heidi M. Ingram; Nancy L. Livesey; J. Brian Power; Michael R. Davey (Acta Physiologiae Plantarum, 2001)

Pheochromocytoma cell lines from heterozygous neurofibromatosis knockout mice - J. F. Powers; M. J. Evinger; P. Tsokas; S. Bedri; J. Alroy; M. Shahsavari; A. S. Tischler (Cell and Tissue Research, 2000)

Stratigraphical distribution of platinum-group minerals in the Eastern Layered Series, Rum, Scotland - M. R. Power; D. Pirrie; J. C. Ø. Andersen; A. R. Butcher (Mineralium Deposita, 2000)

The seasonal cycle in coupled ocean-atmosphere general circulation models - C. Covey; A. Abe-Ouchi; G. J. Boer; B. A. Boville; U. Cubasch; L. Fairhead; G. M. Flato; H. Gordon; E. Guilyardi; X. Jiang; T. C. Johns; H. Le Treut; et al. (Climate Dynamics, 2000)

Plant regeneration from embryogenic cultures of Phragmites australis (Cav.) Trin. Ex Steud. - Csaba Máthé; Márta M. Hamvas; István Grigorszky; Gábor Vasas; Erika Molnár; J. Brian Power; Michael R. Davey; George Borbély (Plant Cell, Tissue and Organ Culture (PCTOC), 2000)

Combined PI–DAPI staining (CPD) reveals NOR asymmetry and facilitates karyotyping of plant chromosomes - S. C. Andras; T. P. V. Hartman; J. Alexander; R. McBride; J. A. Marshall; J. B. Power; E. C. Cocking; M. R. Davey (Chromosome Research, 2000)

Environmental influences on an exploited anadromous Arctic charr stock in Labrador - M. Power; J. B. Dempson; G. Power; J. D. Reist (Journal of Fish Biology, 2000)
Arctic charr Salvelinus alpinus at Nain, Labrador, were influenced by recent variability in measured environmental variables and able to mitigate partially the effects of past conditions in a single year. Weather conditions prevailing during the first winter and sea migration life‐stages also exerted significant influence on measured age and weight characteristics and are argued to play a role in determining the population dynamics of exploited stocks.

Temporal abundance patterns and growth of juvenile herring and sprat from the Thames estuary 1977–1992 - M. Power; M. J. Attrill; R. M. Thomas (Journal of Fish Biology, 2000)
Most herring Clupea harengus and sprat Sprattus sprattus sampled from West Thurrock power station intake screens, middle Thames estuary, between 1977 and 1992 were age‐0 and followed regular patterns of seasonal occurrence. Juvenile herring entered the estuary in July, peaked in abundance November to March, and then declined. Juvenile sprat first appeared in September and peaked in abundance in January. Neither species was abundant in summer samples. While in the estuary, herring and sprat increased in length an average of 4·0 and 0·33 cm respectively. Abundance of both species was significantly affected by temperature, temporal trend, shoaling behaviour and seasonal variables, and of herring by suspended solids. Interactions between environmental variates did not influence the abundance of either species. As estuarine clupeids were influenced by a complex set of events within and outside the estuary, estuarine monitoring studies alone will not be sufficient for understanding the changes in estuarine fish communities resulting from future human activity.

The effect of food deprivation and refeeding on the liver, thyroid hormones and transthyretin in sea bream - D. M. Power; J. Melo; C. R. A. Santos (Journal of Fish Biology, 2000)
There was a significant reduction in body weight of sea bream Sparus aurata and the hepatosomatic index after 3 weeks food deprivation. Liver biochemical indices and morphology were altered by food deprivation, there was a loss of eosin staining in hepatocyte cytoplasm and the appearance of large depleted vacuoles. Cell and nuclear area were significantly reduced ( P T 3 (33·98±12·47 ng ml ‐1 ) and T 4 (16·54±9·5 ng ml ‐1 ) was significantly ( P 0·001) lower than the control (66·52±13·4 and 56·83±7·3, respectively). Refeeding for 1 week restored circulating T 3 ( P 0·05) close to control levels but did not significantly affect the concentration of T 4 . Northern blotting with an homologous probe for transthyretin (TTR) demonstrated clearly the expression of a single mRNA transcript of 0·7 kb for this protein in the liver. The level of TTR message was substantially reduced below control levels in the liver of fasted fish and 1 week refeeding failed to restore expression.

A Drop-spreading Technique to Produce Cytoplasm-free Mitotic Preparations from Plants with Small Chromosomes - S. C. Andras; T. P. V. Hartman; J. A. Marshall; R. Marchant; J. B. Power; E. C. Cocking; M. R. Davey (Chromosome Research, 1999)

Expression of a chimeric nitrate reductase gene in transgenic lettuce reduces nitrate in leaves - I. S. Curtis; J. B. Power; A. M. M. de Laat; M. Caboche; M. R. Davey (Plant Cell Reports, 1999)

Increased stable inheritance of herbicide resistance in transgenic lettuce carrying a petE promoter-bar gene compared with a CaMV 35S-bar gene - M. S. McCabe; F. Schepers; A. van der Arend; U. Mohapatra; A. M. M. de Laat; J. B. Power; M. R. Davey (Theoretical and Applied Genetics, 1999)

Intergeneric somatic hybrids of rice [Oryza sativa L. (+) Porteresia coarctata (Roxb.) Tateoka] - N. B. Jelodar; N. W. Blackhall; T. P. V. Hartman; D. S. Brar; G. Khush; M. R. Davey; E. C. Cocking; J. B. Power (Theoretical and Applied Genetics, 1999)

Evidence for anadromy in a southern relict population of Arctic charr from North America - R. R. Doucett; M. Power; G. Power; F. Caron; J. D. Reist (Journal of Fish Biology, 1999)
Stable isotope analysis of Arctic charr from a southern relict population in Québec showed that some individuals adopted anadromy as a life‐history strategy, but the strategy did not predominate in the population. Differences in length‐at‐age, ages and sex ratios between identified freshwater residents and anadromous individuals were consistent with previous descriptions of partially migratory populations. This suggests that anadromy in relict populations in Québec is associated with niche shift and occurs as a conditional response to opportunities for maximizing the rewards (e.g. fitness) of habitat use.

A stable transformation system for the ornamental plant, Datura meteloides D. C. - I. S. Curtis; J. B. Power; P. Hedden; D. A. Ward; A. Phillips; K. C. Lowe; M. R. Davey (Plant Cell Reports, 1999)

Stress-inducible transgenic nematodes as biomonitors of soil and water pollution - R S Power; H E David; M H A Z Mutwakil; K Fletcher; C Daniells; M A Nowell; J L Dennis; A Martinelli; R Wiseman; E Wharf; D I de Pomerai (Journal of Biosciences, 1998)

Seismic image of the Mount Spurr magmatic system - J. A. Power; A. Villaseñor; H. M. Benz (Bulletin of Volcanology, 1998)

A comparison of methods for direct gene transfer into maize (Zea mays L.) - E. M. Southgate; M. R. Davey; J. B. Power; R. J. Westcott (In Vitro Cellular & Developmental Biology - Plant, 1998)

Shoot regeneration from cultured root explants of spinach (Spinacia oleracea L.): a system for Agrobacterium transformation - K. A. Knoll; K. C. Short; I. S. Curtis; J. B. Power; M. R. Davey (Plant Cell Reports, 1997)

The role of larval retention and transport features in mortality and potential gene flow of walleye pollock - K. M. Bailey; P. J. Stabeno; D. A. Powers (Journal of Fish Biology, 1997)
This paper reviews the physical oceanography in the range of walleye pollock that influences transport and mortality of eggs and larvae, and summarizes the current status of stock structure studies of pollock. A synthesis is presented that links the genetic stock structure and the potential for gene flow due to transport. In the eastern North Pacific Ocean, walleye pollock Theragra chalcogramma consistently spawn in several locations, with the major deposition of planktonic eggs in Shelikof Strait in the Gulf of Alaska and in the eastern Bering Sea, near Unimak Pass. In the Gulf of Alaska, eddies are common features where pollock larvae tend to be concentrated; eddies in the region of Shelikof Strait retain larvae in the region, where they are protected from transport offshore in the Alaska Coastal Current (ACC). The ACC is vigorous in Shelikof Strait (20–50 cm s −1 ), but in the downstream region along the Alaska Peninsula it flows over the continental shelf and is more sluggish (10 cm s −1 ). There is equivocal information on the condition and mortality of larvae inside and outside eddies; there may be seasonal and interannual differences in the direct role of eddies on larval mortality. In some years with extremely high storm activity, resulting in a very energetic ACC, eddies are less prevalent and pollock larvae are swept offshore into the swift flowing Alaskan Stream (50–100 cm s −1 ). In the Alaskan Stream the nutritional condition and growth of larvae is poor, leading to high mortality. Satellite‐tracked drifter trajectories indicate that Alaskan Stream water can enter the Bering Sea through deep Aleutian passes, the nearest (easternmost) being Amutka Pass. Larvae surviving in the Alaskan Stream and carried into the Bering Sea through Amutka Pass would find themselves in the Aleutian Basin, where feeding conditions are poor and where larval mortality has been high. Therefore, geographical barriers (such as the Alaska Peninsula and shallow sills at passes between the Gulf of Alaska and Bering Sea), retention features, and high mortality rates of vagrants are likely to impede gene flow due to larval drift between the Gulf of Alaska and eastern Bering Sea. Recent findings using restriction fragment length polymorphism (RFLP) analysis of mtDNA variation, further supported by differences in nuclear DNA microsatellite loci, indicate distinct genetic stocks in the Bering Sea and Gulf of Alaska. Within the Bering Sea, several geographically separate pollock spawning grounds result in larvae occupying a variety of basin, slope and shelf habitats. Larvae can be concentrated in eddies in slope waters, but on the eastern Bering Sea shelf eddies are uncommon and a persistent mean northwestward flow exists along the 100‐m isobath. Thus, the potential for gene flow through larval drift is much higher. Genetically distinct stocks have not been identified in the eastern Bering Sea, although there is some evidence for their existence.

Somatic embryogenesis and plant regeneration from stem explants of Moricandia arvensis - W. Craig; A. Wiegand; C. M. O'Neill; R. J. Mathias; J. B. Power; M. R. Davey (Plant Cell Reports, 1997)

Carbon dioxide-gassed fluorocarbon enhances micropropagation of rose (Rosa chinesis Jacq.) - J. Wardrop; K. C. Lowe; M. R. Davey; R. Marchant; J. B. Power (Plant Cell Reports, 1997)

Strategies for promoting division of cultured plant protoplasts: synergistic beneficial effects of haemoglobin (Erythrogen) and Pluronic F-68 - P. Anthony; K. C. Lowe; M. R. Davey; J. B. Power (Plant Cell Reports, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Homoeologous pairing and recombination in backcross derivatives of tomato somatic hybrids [Lycopersicon esculentum (+) L. peruvianum] - A. S. Parokonny; J. A. Marshall; M. D. Bennett; E. C. Cocking; M. R. Davey; J. Brian Power (Theoretical and Applied Genetics, 1997)

Factors influencing time to breakdown (TTB) of cooked potato tissue - W. M. Iritani; M. J. Powers; L. Hudson; L. Weller (American Journal of Potato Research, 1977)

Microbial interactions: Population and sporulation studies ofBacillus sphaericus grown in association withErwinia atroseptica - D. A. Power; M. J. Pelczar (Antonie van Leeuwenhoek, 1964)